Artificial leather and its manufacturing method

JP7634959B2Active Publication Date: 2025-02-25ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2020179757
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-10-30
Filing Date
2020-10-27
Publication Date
2025-02-25
Estimated Expiration
2040-10-27

AI Technical Summary

Benefits of technology

【0013】 本発明に係る人工皮革は、風合い(剛軟値)と防しわ性に優れるため、インテリア用、自動車用、航空機用、鉄道車両用等のシートの表皮材又は内装材等、服飾製品等に好適に利用可能である。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007634959000002
    Figure 0007634959000002
  • Figure 0007634959000003
    Figure 0007634959000003
  • Figure 0007634959000004
    Figure 0007634959000004
Patent Text Reader

Abstract

To provide an artificial leather having both feeling (bending resistance) and wrinkle resistance and capable of being suitably used for decoration products including a skin material of a seat or an interior material such as for interior, for automobile, for aircraft, or for railway vehicle.SOLUTION: An artificial leather comprises a fiber sheet and a polyurethane resin. The fiber sheet comprises at least a fiber layer (A) constituting a first outside surface of the artificial leather, and has a cross section polyurethane resin area ratio of 15% or more and 30% or less in a cross section in a thickness direction of the fiber layer (A), and has a standard deviation of the cross section polyurethane resin area ratio of 25% or less.SELECTED DRAWING: Figure 6
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an artificial leather that combines texture (flexibility value) and wrinkle resistance (wrinkle resistance rate), and a method for producing the same. [Background technology]

[0002] Artificial leather, which is composed primarily of a fibrous substrate (fiber sheet) such as nonwoven fabric and polyurethane (hereinafter also referred to as PU resin) resin, has excellent properties that are difficult to achieve with natural leather, such as easy care, functionality, and uniformity, and is suitable for use in clothing, shoes, bags, and also as upholstery and interior materials for seats for automobiles, aircraft, and railway cars, as well as clothing materials such as ribbons and patch substrates.

[0003] Conventionally, a commonly used method for producing such artificial leather involves impregnating a fiber sheet with an organic solvent solution of PU resin, and then immersing the sheet in a non-solvent for the PU resin (e.g., water or an organic solvent) to wet-solidify the PU resin. For example, in the following Patent Document 1, an organic solvent-based PU resin is used in which N,N-dimethylformamide is used as the organic solvent for the PU resin. However, since organic solvents are generally highly harmful to the human body and the environment, there is a strong demand for a method for producing artificial leather that does not use organic solvents.

[0004] In the following Patent Document 2, a method of using a water-dispersed PU resin dispersion in which PU resin is dispersed in water instead of conventional organic solvent-based PU resin is considered, but "the problem is that the sheet-like material obtained by impregnating a fiber sheet with a water-dispersed PU resin dispersion and coagulating the PU resin tends to have a hard texture. One of the main reasons for this is the difference in the coagulation method between the two. That is, the coagulation method of the organic solvent-based PU resin dispersion is a "wet coagulation method" in which the organic solvent in which the PU molecules are dissolved is replaced with water to coagulate the PU molecules, forming a porous film with low density. Therefore, even when the PU resin is impregnated into the fiber sheet and coagulated, the adhesion points between the fiber and the PU resin exist in dots, and the PU resin tends to have a porous structure, resulting in a soft sheet-like material. On the other hand, the water-dispersed PU resin is a "dry heat coagulation method" in which the hydration state of the PU molecules dispersed in water is broken down by heating, and the PU molecules are coagulated by coagulating each other, and the resulting PU film structure is a non-porous film with high density. As a result, the adhesion between the fibers and the PU resin becomes dense, and the entangled parts of the fibers are strongly gripped, resulting in a hard texture. Based on the recognition that a technique for making the PU resin in a sheet-like material have been proposed to improve the texture by using this water-dispersed PU resin, i.e., to suppress the grip of the entangled parts of the fibers by the PU resin, a method for producing a sheet-like material, which is characterized by applying a PU resin dispersion containing a water-dispersed PU resin, a foaming agent, and an anionic surfactant and / or an amphoteric surfactant to a fiber sheet, is disclosed that a porous structure of the PU resin can be expressed inside the sheet-like material, regardless of the type of foaming agent and PU resin, and that a sheet-like material can be produced that has a uniform nap length equivalent to that of artificial leather using an organic solvent-based PU resin, an elegant surface quality with an excellent fiber density, and a good texture that is soft and has excellent resilience. However, in the sheet-like material obtained by the method described in Patent Document 2, the gaps between the ultrafine fiber bundles and the PU resin are large (the PU resin has a porous structure), and strong adhesion of the PU resin to the ultrafine fiber bundles is inhibited. As a result, although a softer texture is observed in some areas, the cross-sectional PU resin area ratio is still relatively high, and the dispersibility of the PU resin is insufficient. Furthermore, the wrinkle resistance and dispersibility of single fibers have not been investigated.

[0005] In addition, the following Patent Document 3 discloses a sheet-like material made of a nonwoven fabric made of ultrafine fibers having an average single fiber diameter of 0.3 to 7 μm and an elastic resin, in order to provide a sheet-like material with a texture excellent in flexibility and high resistance to folding wrinkles while being flexible, the sheet-like material has a nap on the surface, the elastic resin has a porous structure, and the ratio of micropores having a pore diameter of 0.1 to 20 μm to all pores of the porous structure is 60% or more. Patent Document 3 describes that such a porous structure can adopt interconnected holes and closed bubbles, and that by having a certain ratio or more of micropores in the elastic resin, the flexibility of the elastic resin is increased, and when the sheet-like material is bent and deformed, the deformation force can be distributed and received by the entire elastic resin, not by a part of it, so that the occurrence of folding wrinkles accompanied by buckling of the elastic resin is suppressed, and a sheet-like material having excellent resistance to folding wrinkles can be obtained. It is also described that such a porous structure can be obtained by applying the PU resin to a nonwoven fabric, for example by immersing the nonwoven fabric in a solution of the PU resin dissolved in an organic solvent such as N,N'-dimethylformamide or dimethylsulfoxide, and then subjecting the nonwoven fabric to wet coagulation by immersing the fabric in a non-soluble solvent or a mixture of a soluble solvent and a non-soluble solvent. In this way, in Patent Document 3, an organic solvent (dimethylformamide)-based PU resin is used as the PU resin with which the nonwoven fabric is impregnated, rather than a water-dispersed PU resin, and therefore the problem encountered with the water-dispersed PU resin described above, namely, "the PU resin film structure obtained by the dry heat coagulation method, in which the hydration state of a PU resin dispersion dispersed in water is destroyed by heating and the PU molecules are coagulated by agglomerating together, becomes a high-density non-porous film, and the dispersibility of the PU resin mass deteriorates," does not occur in the first place, and it is assumed that the adhesion between the fibers and the PU resin will be in the form of dots, resulting in a soft sheet-like material. Thus, Patent Document 3 describes that the porous structure of the PU resin achieves both flexibility and resistance to folding and wrinkling, but the artificial leather described does not relate to an artificial leather filled with a water-dispersible PU resin, and the cross-sectional PU resin area ratio and the dispersibility of single fibers are not considered.

[0006] The following Patent Document 4 discloses a sheet-like material having high mechanical properties, flexibility, light weight, and quality, a manufacturing method thereof, and a grain-finished artificial leather having high mechanical properties, texture (flexibility), light weight, and excellent flex resistance, the sheet-like material comprising a nonwoven fabric mainly made of ultrafine hollow fibers with an average single fiber diameter of 0.05 to 10 μm and an elastic polymer as constituent components, the ultrafine hollow fibers having 2 to 60 hollow parts. The document describes that by applying ultrafine fibers having hollow parts to artificial leather, a sheet-like material suitable for artificial leather is obtained that combines high mechanical properties and texture (flexibility) similar to solid fibers and the light weight due to hollow fibers, and that by applying the ultrafine fibers to grain-finished artificial leather, grain-finished artificial leather is obtained that combines high mechanical properties and texture (flexibility) similar to solid fibers, the light weight due to hollow fibers, and quality due to the flexibility of the fibers, and has excellent flex resistance. Patent Document 4 describes that the hollow portion can be formed from precisely controlled islands-in-the-sea type composite fibers, and that the covering layer (grain surface layer) is formed by using a method such as coating a fiber sheet with a PU resin solution. Patent Document 4 also describes that a PU resin mass is obtained by applying PU resin to a fiber sheet by immersing the fiber sheet in a solution of PU resin dissolved in an organic solvent such as N,N'-dimethylformamide or dimethyl sulfoxide, and then immersing the sheet in a non-soluble solvent or a mixture of a soluble solvent and a non-soluble solvent for wet coagulation. Thus, in Patent Document 4, an organic solvent (dimethylformamide)-based PU resin is used as the PU resin with which the nonwoven fabric is impregnated, rather than a water-dispersed PU resin, and therefore the problem that occurs when using the water-dispersed PU resin described above, namely, "the PU resin film structure obtained by the dry heat coagulation method, in which the hydration state of the PU resin dispersion dispersed in water is destroyed mainly by heating and the PU molecules are coagulated by agglomerating together, becomes a high-density nonporous film, and the dispersibility of the PU resin mass deteriorates," does not occur in the first place, and it is assumed that the adhesion between the fibers and the PU resin becomes dot-like, resulting in a soft sheet-like material. Patent Document 4 examines the relationship between the number of hollow parts and the texture and flex resistance of the obtained artificial leather, but the artificial leather described does not relate to an artificial leather filled with a water-dispersible PU resin, and the cross-sectional PU resin area ratio and the dispersibility of single fibers are not examined.

[0007] Furthermore, the following Patent Document 5 discloses an artificial leather made of a nonwoven fabric of ultrafine fibers and a polymer elastomer, which is free from color unevenness between the ultrafine fibers and the PU resin, has a resilient feel, is smooth to the touch, and is uniform and has excellent surface quality. The artificial leather comprises a nonwoven fabric of ultrafine fibers having an average single fiber fineness of 0.01 to 0.50 dtex and a polymer elastomer, and is characterized in that the artificial leather contains 10 to 50 mass% of the polymer elastomer, and in a cross section obtained by cutting the artificial leather perpendicularly to the surface direction, the number of polymer elastomer agglomerates having a size of 100 μm or more in the thickness direction, which are present within 200 μm in the thickness direction from the surface excluding the napped portion of the artificial leather, per cross-sectional length in the surface direction is 0.1 to 2.5 pieces / mm. The method for producing the artificial leather also discloses a process for passing a water flow through the inside of a nonwoven fabric of ultrafine fibers to disperse the ultrafine fibers. Patent Document 5 describes that in order to eliminate color spots on the surface of artificial leather resulting from the difference in color tone between the ultrafine fibers and the polymer elastomer, it is effective to disperse the ultrafine fibers during the production process and to adjust the size of the resin agglomerates of the polymer elastomer present inside the artificial leather to an appropriate range, and that as a treatment for dispersing the ultrafine fibers, a method of passing a water current through the inside of an ultrafine fiber sheet in a liquid is preferably used, and that the ultrafine fibers are dispersed by applying a mechanical impact to a bundle of ultrafine fibers with the water current; specifically, a device such as a vibro washer can be used, and that the vibro washer is preferable in that it can perform a uniform dispersion treatment over the entire surface of the sheet, but that a method such as a water jet punch that applies a mechanical impact by a localized high-pressure water current outside a liquid bath is not preferable, because in the water jet punch treatment, the liquid passes locally, making it difficult to perform a uniform treatment, and even when the number of nozzles is increased, there is a tendency for regular streaky appearance defects to occur in the length direction, resulting in an artificial texture of the artificial leather. In the examples of Patent Document 5, there is a description regarding a dispersion treatment of ultrafine fibers that "the sea component of the islands-in-sea type composite fiber was removed, and the fiber sheet after the sea component removal, in which ultrafine fibers were produced, was treated with a vibro washer, and a water flow was passed through the inside of the sea-removed sheet in water, thereby performing a dispersion treatment of the ultrafine fibers," but no details of the treatment conditions are described at all.In a general dispersion process, fiber bundles still remain, and the presence of fibers dispersed together with the fiber bundles during the nap raising process results in an uneven dense feel and raised nap. Also, it is described that if the number of polymeric elastomer resin agglomerates with a size of 100 μm or more in the thickness direction present within 200 μm from the surface per cross-sectional length in the surface direction is 0.1 to 2.5 pieces / mm, the appearance quality (color tone) is more uniform, but no consideration is given to the cross-sectional PU resin area ratio and its standard deviation, much less the dispersibility of single fibers. Furthermore, in Patent Document 5, an organic solvent (dimethylformamide)-based PU resin is used as the PU resin with which the sheet-like material is impregnated, rather than a water-dispersed PU resin. Therefore, the problem that occurs when using the water-dispersed PU resin described above, namely, "the PU resin film structure obtained by the dry heat coagulation method, in which the hydration state of the PU resin dispersion dispersed in water is destroyed mainly by heating and the PU resin dispersions are coagulated by agglomerating with each other, becomes a high-density non-porous film, and the dispersibility of the PU resin mass deteriorates," does not occur in the first place, and it is assumed that the adhesion between the fibers and the PU resin will be in dots, resulting in a soft sheet-like material.

[0008] On the other hand, the following Patent Document 6 discloses a method for producing artificial leather, which uses a water-dispersed PU resin dispersion that does not use organic solvents, and is characterized in that a fibrous substrate to be used for the artificial leather is coated or impregnated with a polymer solution in a PU resin dispersion state that exhibits elasticity when fixed, and then the polymer solution impregnated in the fibrous substrate is fixed into the fibrous substrate by using a combination of moist heat and microwaves, with the aim of obtaining artificial leather that is soft and has a quality similar to that of natural leather. Patent Document 6 describes that the PU resin, which is an elastic polymer, is fixed more uniformly by irradiating microwaves, and that the fixed PU resin itself has many voids (porosity), so that the feel of the sheet-like material immediately after wet heat fixing is softer and more durable than that obtained by conventional dry fixing (curing). Although Patent Document 6 describes that microwave treatment improves the texture of artificial leather, it does not consider wrinkle resistance, let alone the cross-sectional PU resin area ratio or the dispersion of single fibers.

[0009] Cushioning is required for artificial leather used in car seats and other automotive applications. For this reason, PU resin, a rubber elastic body, is used in leather. Increasing the amount of PU resin increases cushioning and wrinkle resistance, but the leather becomes hard and the texture (flexibility) is lost. As described above, in Patent Document 3, by subjecting an organic solvent-based PU resin to a foaming treatment, the amount of PU resin adhering to the fibers can be reduced, and the amount of PU resin, which is a rubber elastic body inside the leather, can be increased while preventing the leather from becoming hard, thereby obtaining leather with good wrinkle resistance. However, when a water-dispersed PU resin is used, the artificial leather obtained is more likely to be hard than when an organic solvent-based PU resin is used, and further improvement is needed. As described above, in the prior art, attempts have been made to provide artificial leathers excellent in texture (bend value) and wrinkle resistance obtained by wet coagulation of an organic solvent-based PU resin on a fiber sheet using islands-in-the-sea fibers, or to provide artificial leathers excellent in texture (bend value) obtained by applying microwaves to the drying of a sheet-like material obtained by heat-sensitive coagulation of a water-dispersible PU resin. However, even in the case of artificial leathers obtained using a water-dispersible PU resin, an artificial leather having a satisfactory level of both texture (bend value) and wrinkle resistance and a method for producing the same have not yet been achieved. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] Patent No. 4089324 [Patent Document 2] JP 2014-25165 A [Patent Document 3] International Publication No. 2018 / 135243 [Patent Document 4] International Publication No. 2016 / 031624 [Patent Document 5] JP 2016-69790 A [Patent Document 6] International Publication No. 99 / 18281 Summary of the Invention [Problem to be solved by the invention]

[0011] In view of the problems of the prior art described above, the problem to be solved by the present invention is to provide an artificial leather which is less harmful to the human body and the environment and which has both a satisfactory level of texture (flexibility value) and wrinkle resistance. [Means for solving the problem]

[0012] As a result of intensive research and repeated experiments conducted by the present inventors in order to solve the above problems, they unexpectedly discovered that an artificial leather having the following characteristics could solve the above problems, and thus completed the present invention. That is, the present invention is as follows. [1] An artificial leather comprising a fiber sheet and a polyurethane resin, the fiber sheet comprising at least a fiber layer (A) constituting a first outer surface of the artificial leather, the fiber layer (A) having a cross-sectional polyurethane resin area ratio of 15% or more and 30% or less in a thickness direction cross section, and the cross-sectional polyurethane resin area ratio having a standard deviation of 25% or less. [2] The artificial leather according to [1], wherein the k-nearby distance ratio value (k=9, radius r=20 μm) between the cross sections of the single fibers constituting the fiber layer (A) in the thickness direction cross section of the artificial leather is 10% or more and 80% or less. [3] The artificial leather according to [1] or [2], wherein the fiber sheet has a two or more layer structure composed of a fiber layer (A) constituting the first outer surface and a scrim and / or fiber layer (B) in contact with the fiber layer (A). [4] The artificial leather according to any one of the above [1] to [3], wherein the average diameter of the single fibers constituting the fiber layer (A) is 1.0 μm or more and 8.0 μm or less. [5] The artificial leather according to any one of the above [1] to [4], wherein the polyurethane resin is a water-dispersible polyurethane resin. [6] The artificial leather according to any one of [1] to [5], wherein the adhesion rate of the polyurethane resin to the fiber sheet is 15% by mass or more and 50% by mass or less. [7] The artificial leather according to any one of [1] to [6] above, which has a bending resistance of 28 cm or less. [8] The artificial leather according to any one of [1] to [7] above, which has a wrinkle resistance rate of 60% or more according to JIS L 1059-1:2009 "Test methods for wrinkle resistance of textile products-Part 1: Measurement of recovery from horizontal folding wrinkles (Monsanto method)". [9] The artificial leather according to any one of [1] to [8], wherein the fiber sheet is made of polyester fiber.

[10] The following steps: forming a fiber web from the islands-in-sea staple fibers, and then needle-punching the resulting fiber sheet to obtain a sea-removal treatment to obtain a fiber sheet in which the island component single fibers are exposed; and a step of subjecting the obtained fiber sheet to a water jet dispersion treatment to obtain a fiber sheet in which single fibers are dispersed; The method for producing the artificial leather according to any one of the above [1] to [9],

[11] The process of: a step of impregnating the fiber sheet having the dispersed single fibers with a water-dispersed polyurethane resin dispersion liquid containing hot water-soluble resin particles; The method according to

[10] above, further comprising:

[12] The process of: a step of impregnating the fibers with a water-dispersed polyurethane resin dispersion, further subjecting the fibers to a wet heat treatment and then drying in combination with microwaves to fix the polyurethane resin to the fibers, thereby obtaining a sheet-like material filled with the polyurethane resin; The method according to

[10] or

[11] above, further comprising:

[13] The method according to any one of

[10] to

[12] above, wherein the fiber web contains hot-water-soluble resin fibers.

[14] The method according to

[13] above, wherein the hot water soluble resin of the hot water soluble resin microparticles and the hot water soluble resin fiber are both polyvinyl alcohol resin.

[15] The method according to any one of

[10] to

[14] above, wherein the water jet dispersion treatment is carried out using a plurality of nozzles having a nozzle hole spacing of 1.0 mm or less and a nozzle hole diameter of 0.05 mm or more and 0.30 mm or less.

[16] The method according to any one of

[10] to

[15] above, wherein the water jet dispersion treatment is carried out using a plurality of nozzles that eject a water jet having a disturbance of 10% or more.

[17] The method according to any one of

[11] to

[16] above, wherein the water-dispersed polyurethane resin dispersion has a solid content of 10% by weight or more and 35% by weight or less.

[18] The method according to any one of

[11] to

[17] above, wherein the content of hot water-soluble resin microparticles in the water-dispersed polyurethane resin dispersion is 1% by weight or more and 20% by weight or less. Effect of the Invention

[0013] The artificial leather according to the present invention has excellent texture (flexibility) and wrinkle resistance, and can therefore be suitably used for interior materials, such as seat coverings or interior materials for automobiles, aircraft, railway cars, etc., clothing products, etc. [Brief description of the drawings]

[0014] [Figure 1] 1 is a conceptual diagram showing an example of the structure of artificial leather. Since the scrim 11 and the fiber layer (B) 13 are optional, the artificial leather of this embodiment may be a single layer of the fiber layer (A) 12, a two-layer structure of the fiber layer (A) and the scrim or the fiber layer (B), or a three-layer structure of the fiber layer (A), the scrim, and the fiber layer (B). [Diagram 2] FIG. 2 is a conceptual diagram illustrating how to determine the average diameter of the single fibers constituting the fiber layer (A). [Diagram 3]FIG. 3 is a conceptual diagram illustrating sample collection locations for the single fiber cross section k neighborhood distance ratio (%), cross-sectional PU resin area ratio, average diameter of single fibers, surface PU resin area ratio on the first outer surface, and spatial size in the thickness direction cross section of the fiber layer (A). [Figure 4] FIG. 4 is an image showing a state in which each single fiber cross section within a specified image area has been manually marked in order to determine the single fiber cross section k neighborhood distance ratio value (%) in the thickness direction cross section. [Diagram 5] FIG. 5 is a conceptual diagram for explaining how to determine the single fiber cross section k neighborhood distance ratio (%) in the thickness direction cross section. [Figure 6] FIG. 6 is a conceptual diagram for explaining how to determine the cross-sectional or surface PU resin area ratio and its standard deviation. [Figure 7] FIG. 7 is a conceptual diagram showing the nozzle hole intervals when a plurality of nozzle holes used in water flow dispersion treatment are arranged in one row or in two or more rows. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] Hereinafter, the embodiments of the present invention will be described in detail, but the present invention is not limited to the embodiments. In addition, unless otherwise specified, various values ​​in the present disclosure are values ​​obtained by the method described in the [Examples] section of the present disclosure or a method that is understood to be equivalent to the above by a person skilled in the art.

[0016] <Artificial leather> One embodiment of the present invention is an artificial leather comprising a fiber sheet and a PU resin, the fiber sheet comprising at least a fiber layer (A) constituting a first outer surface of the artificial leather, the artificial leather having a PU resin area ratio in a thickness direction cross section (cross-sectional PU resin area ratio) of 15% or more and 30% or less, and a standard deviation of the cross-sectional PU resin area ratio of 25% or less.

[0017] In this specification, "artificial leather" means "a substrate made of special nonwoven fabric (mainly a fiber layer having a random three-dimensional structure, impregnated with PU resin or a similar polymeric elastomer having flexibility)" according to the Household Goods Quality Labeling Law. In addition, according to the definition of JIS-6601, artificial leather is classified into "smooth" having a grain-like appearance of leather and "napped" having an appearance of suede, velour, etc. of leather, depending on its appearance. The artificial leather of this embodiment relates to one classified as "napped" (i.e., suede-like artificial leather having a brushed appearance). The suede-like appearance can be formed by buffing (brushing) the outer surface of the fiber layer (A) (i.e., the surface that will become the first outer surface of the artificial leather) with sandpaper or the like. In this specification, the first outer surface of the artificial leather means the surface that is exposed to the outside when the artificial leather is used (for example, the surface that comes into contact with the human body in the case of a chair application) (see Fig. 1 and Fig. 3). In one embodiment, in the case of a suede-like artificial leather, the first outer surface is raised or napped by buffing or the like. In this specification, unless otherwise specified, the term "fiber web" refers to the state before entanglement of short fibers, the term "fiber sheet" refers to the state after entanglement and before filling with PU resin, the term "sheet-like material" refers to the state after filling with PU resin and before dyeing and finishing, and the term "artificial leather" refers to the state of the product after dyeing and finishing. The term "nonwoven fabric" includes "fiber web," "fiber sheet," "sheet-like material," and "artificial leather," and the term "fibrous substrate" includes not only the term "nonwoven fabric," but also woven and knitted fabrics, etc.

[0018] [Cross-sectional PU resin area ratio in the thickness direction cross section of fiber layer (A) and its standard deviation] In the artificial leather of this embodiment, the cross-sectional PU resin area ratio in the thickness direction cross section of the fiber layer (A) is 15% or more and 30% or less, and the standard deviation of the cross-sectional PU resin area ratio is 25% or less. If the cross-sectional PU resin area ratio exceeds 30%, the PU resin adhesion rate becomes too high, the artificial leather has a strong rubber-like feel, and the wrinkle resistance is improved, but the texture (bending resistance value) deteriorates and becomes hard. If the cross-sectional PU resin area ratio is less than 15%, the texture (bending resistance value) is good, but the wrinkle resistance is reduced. In addition, when the artificial leather does not have a scrim, the cross-sectional PU resin area ratio is 15% or more, since sufficient mechanical properties in the planar direction are easily obtained. The cross-sectional PU resin area ratio is preferably 15% or more and 28% or less, more preferably 15% or more and 26% or less.

[0019] The cross-sectional PU resin area ratio, together with the k-near distance ratio value (k=9, radius r=20 μm) described later, indexes the texture (stiffness value) and wrinkle resistance described below. For example, when the k-near distance ratio value (k=9, radius r=20 μm) exceeds 80%, there is an excess of single fiber bundles. On the other hand, the water-dispersible PU resin has a strong tendency to adhere to the single fibers and single fiber bundles. In other words, in the presence of an excess of single fiber bundles with a k-near distance ratio value of 80% or more, the PU resin masses aggregate and adhere to the single fiber bundles, improving the wrinkle resistance, but the texture (stiffness value) tends to deteriorate. On the other hand, when the k-near distance ratio value is less than 10%, the single fibers are excessively dispersed, and the PU resin is also excessively dispersed, resulting in insufficient adhesion between the fibers by the PU resin, which deteriorates the wrinkle resistance, makes it difficult to obtain a leather-like texture, and also makes it difficult to obtain sufficient mechanical properties. If the k neighborhood distance ratio value (k=9, radius r=20 μm) described later is 10% or more and 80% or less, the single fibers are appropriately dispersed, making it easy to obtain good texture (stiffness / softness value) and wrinkle resistance.

[0020] As will be described later (see Figure 6), the cross-sectional PU resin area ratio was determined by binarizing the PU resin in the SEM image as a black area, determining the area ratio of PU resin for each section from the obtained binarized image by the section method, and averaging the cross-sectional PU resin area ratios (%) for all sections, with the standard deviation indicating the variation from the average for all sections.

[0021] The artificial leather of this embodiment is characterized in that the standard deviation of the cross-sectional PU resin area ratio in the thickness direction cross section of the artificial leather is 25% or less. If the standard deviation of the cross-sectional PU resin area ratio is 25% or less, the PU resin agglomerates attached to the fibers are uniformly attached, improving the texture (bending softness value). In other words, by uniformly finely finely adhering the PU resin to the fibers in the thickness direction cross section of the artificial leather, the fine PU resin agglomerates around the fibers become cushions, and good wrinkle resistance is obtained. In addition, since there are few parts where the PU resin excessively grips the fibers or where the PU resin agglomerates are excessively unevenly distributed, a good texture (bending softness value) is obtained and the variation in the texture (bending softness value) is also small. The standard deviation of the cross-sectional PU resin area ratio is preferably 22% or less, more preferably 20% or less, and even more preferably 16% or less. The lower limit of the standard deviation of the cross-sectional PU resin area ratio is not particularly limited, and may be 0% or more.

[0022] As will be described later, for example, a fiber web having dispersed single fibers is impregnated with an aqueous PU resin dispersion containing hot water-soluble resin microparticles such as polyvinyl alcohol resin microparticles (hereinafter also referred to as PVA resin microparticles), and then the PU resin is fixed to the fibers by using microwaves in combination during drying after wet heat treatment to obtain a fiber web filled with PU resin, and / or islands-in-the-sea type staple fibers are mixed with hot water-soluble resin fibers and the hot water-soluble resin fibers and the hot water-soluble resin microparticles (e.g., PVA resin microparticles) are eluted in a subsequent process, for example, during dyeing, whereby the standard deviation of the cross-sectional PU resin area ratio can be controlled to 25% or less. In addition, by carrying out wet heat coagulation under conditions of a water vapor temperature of 100°C or higher and 110°C or lower for a treatment time of 1 to 5 minutes, and by carrying out microwave treatment under conditions of a microwave output of 10 kW for a treatment time of 1 to 5 minutes, the PU resin becomes porous, and the hot water-soluble resin fibers and hot water-soluble resin microparticles (e.g., PVA resin microparticles) are eluted during dyeing, and the hot water-soluble resin fibers and hot water-soluble resin microparticles adjacent to the PU resin disappear, making the PU resin porous and fine, and also promoting point-like adhesion with the fibers, resulting in a good texture (stiffness / softness value) and improved wrinkle resistance.

[0023] Also, for example, a web may be formed from islands-in-sea staple fibers, and then a needle punching process may be performed to remove entangled fibers from the resulting fiber sheet to obtain a fiber sheet in which island component single fibers are exposed. The fiber web may then be subjected to a water flow dispersion process described below to obtain a fiber web in which single fibers are dispersed. As the single fibers are dispersed, the PU resin attached to the fibers is also dispersed, and the standard deviation of the cross-sectional PU resin area ratio can be controlled to 25% or less.

[0024] [k-neighborhood distance ratio value between the cross sections of the single fibers that make up the fiber layer (A) (k = 9, radius r = 20 μm)] In this embodiment, the k-neighborhood distance ratio value (k=9, radius r=20 μm) between the cross sections of the single fibers constituting the fiber layer (A) in the thickness direction cross section of the artificial leather is preferably 10% to 80%. The k-neighborhood distance ratio value (k=9, radius r=20 μm) indicates the density of the single fibers. The measurement method will be described later, but the k-nearest neighbor method is a method in which k single fiber cross sections close to an arbitrary single fiber cross section are taken, and the k-th closest radius in Euclidean distance (i.e., the square root of the sum of the squares of the distances in the X and Y directions (=shortest distance)) is used as the decision boundary. In this embodiment, an SEM image is taken, and it is determined whether the k=9th closest single fiber cross section exists within a distance of a radius of 20 μm from the approximate center of an arbitrary single fiber cross section. The presence or absence of all single fiber cross sections in one SEM image is determined, and the single fiber cross section k=9 neighborhood distance percentage value (%) is calculated using the following formula: Nearby distance percentage value (%) of single fiber cross section (k = 9) = {(number of single fiber cross sections in which the k = 9th closest single fiber cross section exists within a distance of a radius of 20 μm from approximately the center of the single fiber cross section) / (total number of single fiber cross sections in one SEM image)} × 100. If the k-near distance ratio value (k=9, radius r=20 μm) between the cross sections of the single fibers constituting the fiber layer (A) in the thickness direction cross section of the artificial leather is 10% or more, the single fibers are present in a moderately dispersed state, and as a result, the PU resin masses of the fiber layer (A) are also present in a moderately dispersed state, and when the artificial leather is touched with a fingertip, the moderately dispersed fibers are touched, resulting in a satisfactory raised feel. On the other hand, if the k-near distance ratio value (k=9, radius r=20 μm) is 80% or less, the coarse PU resin masses are not excessive, so the surface does not feel rough to the touch, and the large PU resin masses do not adhere to the fibers in the cross section, so the texture (bending softness value) does not deteriorate. The k-near distance ratio value (k=9, radius r=20 μm) is more preferably 20% or more and 70% or less, and even more preferably 30% or more and 60% or less.

[0025] As described below, a fiber web is formed from sea-island staple fibers, and then the resulting fiber sheet is subjected to a sea-removal process to obtain a fiber sheet in which island component single fibers are exposed. The fiber sheet is then subjected to a water flow dispersion process to obtain a fiber sheet in which single fibers are dispersed, thereby controlling the k-near distance ratio value (k=9, radius r=20 μm) to within a range of 80% or less. The water flow dispersion process is preferably carried out by spraying high-pressure water using multiple nozzles with a nozzle hole spacing of 1.00 mm or less. As shown in FIG. 7, the nozzle hole spacing is the distance in the nozzle width direction between a nozzle hole and the nozzle hole most adjacent to the nozzle hole in the nozzle width direction (the same applies when there are two or more rows of nozzle holes as when there is one row). By setting the nozzle hole spacing to 1.00 mm or less, a water flow with a dense spacing can be discharged onto the fiber sheet, and the single fibers in the state of single fiber bundles are dispersed, which makes it easy to improve the denseness and moistness. In addition, the water flow trajectory caused by the water flow dispersion process is less noticeable on the surface of the fiber sheet. The nozzle hole interval is preferably 0.60 mm or less, and more preferably 0.30 mm or less.

[0026] The number of nozzle holes opened in the width direction of the water flow dispersion treatment equipment may be one or more than two. When performing water flow dispersion treatment, it is common to remove the water introduced into the fiber sheet by the water flow dispersion treatment from the viewpoint of maintaining the uniformity and shape stability of the fiber sheet, and dewatering is performed from the opposite side of the water flow dispersion treatment side by a suction method or the like. In that case, for example, when there is one nozzle row and the nozzle hole interval is narrowed, the dewatering capacity is insufficient for the amount of water introduced, and as a result, the uniformity and shape stability of the fiber sheet may deteriorate. On the other hand, it is preferable to reduce the amount of water introduced per nozzle hole row by increasing the number of rows and widening the nozzle hole interval per nozzle hole row, because this makes it easy to balance the amount of water introduced and the dewatering capacity. For example, if poor dewatering occurs with a single-row nozzle with a nozzle hole spacing of 0.30 mm, a two-row nozzle with a nozzle hole spacing of 0.60 mm in one row can be used, with the second row having a phase difference of 0.30 mm with respect to the first row and a nozzle hole spacing of 0.60 mm, resulting in a water flow trajectory (nozzle hole spacing) of 0.30 mm, which is effective in improving poor dewatering. In addition, widening the nozzle hole spacing and using multiple rows is also preferable because it makes nozzle machining (hole opening processing) easier. Equal nozzle hole spacing (water flow trajectory) is preferable because it makes it easier to uniformly distribute single fibers, the water flow trajectory is less noticeable, and the surface quality is good. When there are multiple nozzle rows, the distance between the nozzle rows is preferably set to, for example, a distance equivalent to the nozzle hole interval within one nozzle row in terms of dewatering.

[0027] The hole diameter of the high-pressure water injection nozzle in the water flow dispersion treatment is preferably 0.05 mm or more and 0.30 mm or less, more preferably 0.05 mm or more and 0.20 mm or less, and even more preferably 0.08 mm or more and 0.13 mm or less, from the viewpoints that a high degree of single fiber dispersion can be easily obtained, the water flow trajectory is less noticeable, and furthermore, the amount of water added is not excessive and a balance with the dewatering capacity can be easily achieved. In addition, the water pressure of the water flow dispersion treatment is preferably 1.0 to 10.0 MPa. By setting the water pressure of the water flow dispersion treatment to 1.0 MPa or more, the single fiber bundles are not excessively dispersed, so that it is easy to control the k-near distance ratio value to 10% or more and 80% or less. In addition, the single fibers in the state of single fiber bundles are easily dispersed, and by setting the water pressure of the water flow dispersion treatment to 10.0 MPa or less, the single fibers in the state of single fiber bundles are dispersed, and the water flow trajectory is easily made less noticeable. When the water pressure of the water flow dispersion treatment is high, the water flow may penetrate the fiber sheet, and it may not be used as energy to disperse the single fiber bundles, and the dispersion effect of the single fiber bundles may be reduced compared to when the water pressure is low. In addition, when the water pressure of the water flow dispersion treatment is high, the fiber sheet becomes dense and the texture (stiffness value) tends to deteriorate. The water pressure of the water flow dispersion treatment is more preferably 1.5 to 7.0 MPa, and even more preferably 2.0 to 4.5 MPa.

[0028] As for the shape of the water stream discharged from the nozzle holes, it is also preferable to use a plurality of nozzles that discharge a water stream with a water stream disturbance of 10% or more. Disturbance is an index of the variation in the diameter of the water stream. Since the energy of the water stream can be efficiently converted into the dispersion of fibers, the disturbance is preferably 12% or more, and more preferably 15% or more. The disturbance is calculated by the following formula, where W is the average diameter of the water stream in the range from 28 mm to 35 mm from the nozzle hole outlet, and σ is the standard deviation of the average diameter: Disturbance(%)=σ(mm) / W(mm)×100 It is calculated as follows. Although the mechanism by which disturbance disperses the single fiber bundles is not clear, the inventors of the present application believe that when disturbance is large compared to when it is small, the water flow energy is more likely to be dispersed in multiple directions, including the horizontal direction in addition to the vertical direction of the fiber sheet, and the water flow energy can be efficiently converted into dispersed energy for the single fiber bundles, resulting in a higher dispersion effect.As an example, they believe that with high water pressure, water flow energy that would be wasted by penetrating the fiber sheet is more likely to be captured as dispersed energy.

[0029] In addition, moving the high-pressure water jet nozzle in a circular motion or moving it back and forth at right angles to the process direction (machine direction) also promotes dispersion of the single fibers, resulting in dot-like adhesion between the fibers and the PU resin, which is preferable in terms of improving wrinkle resistance and texture (stiffness / softness value). The distance from the high-pressure water jet surface to the material to be treated is preferably 5 mm or more and 100 mm or less, more preferably 10 mm or more and 60 mm or less, and even more preferably 20 mm or more and 40 mm or less, from the viewpoints of the dispersion effect of the single fiber bundles, the distribution before the water flow dispersion treatment, and the process passability during the water flow dispersion treatment.

[0030] [Adhesion rate of PU resin to fiber sheet] In the artificial leather of this embodiment, the adhesion rate of the PU resin to the fiber sheet is preferably 15% by mass or more and 50% by mass or less, more preferably 22% by mass or more and 45% by mass or less, and even more preferably 26% by mass or more and 40% by mass or less. The ratio of the PU resin to the fiber sheet affects the above-mentioned cross-sectional PU resin area ratio. When the ratio of the PU resin is low, the cross-sectional PU resin area ratio tends to be low. On the other hand, when the ratio of the PU resin is high, the cross-sectional PU resin area ratio tends to be high. If the ratio of the PU resin to the fiber sheet is 15% by mass or more, the fibers are well held by the PU resin and the cushioning property of the artificial leather is increased by the PU resin, so that mechanical strength such as abrasion resistance and wrinkle resistance that meets market needs are easily obtained. On the other hand, if the ratio of the PU resin to the fiber sheet is 50% by mass or less, a soft texture is easily obtained.

[0031] [Polyurethane (PU) resin] The PU resin is preferably one obtained by reacting a polymer diol, an organic diisocyanate, and a chain extender. As the polymer diol, for example, polycarbonate-based, polyester-based, polyether-based, silicone-based, fluorine-based, etc. diols can be adopted, and copolymers of two or more of these may be used. From the viewpoint of hydrolysis resistance, polycarbonate-based, polyether-based, or a combination thereof diol is preferably used. Also, from the viewpoint of light resistance and heat resistance, polycarbonate-based, polyester-based, or a combination thereof diol is preferably used. Furthermore, from the viewpoint of cost competitiveness, polyether-based, polyester-based, or a combination thereof diol is preferably used. Polycarbonate diols can be produced by, for example, transesterification of alkylene glycol with a carbonate ester, or reaction of phosgene or a chloroformate with an alkylene glycol.

[0032] Examples of the alkylene glycol include linear alkylene glycols such as ethylene glycol, propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,9-nonanediol, and 1,10-decanediol; branched alkylene glycols such as neopentyl glycol, 3-methyl-1,5-pentanediol, 2,4-diethyl-1,5-pentanediol, and 2-methyl-1,8-octanediol; alicyclic diols such as 1,4-cyclohexanediol; and aromatic diols such as bisphenol A. These can be used alone or in combination of two or more. Examples of polyester diols include polyester diols obtained by condensing various low molecular weight polyols with polybasic acids. The low molecular weight polyol may be, for example, one or more selected from ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,3-butanediol, 1,4-butanediol, 2,2-dimethyl-1,3-propanediol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, 1,8-octanediol, diethylene glycol, triethylene glycol, dipropylene glycol, tripropylene glycol, cyclohexane-1,4-diol, and cyclohexane-1,4-dimethanol. Also usable are adducts of various alkylene oxides added to bisphenol A. Examples of the polybasic acid include one or more acids selected from the group consisting of succinic acid, maleic acid, adipic acid, glutaric acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, dodecanedicarboxylic acid, phthalic acid, isophthalic acid, terephthalic acid, and hexahydroisophthalic acid.

[0033] Examples of the polyether diol include polyethylene glycol, polypropylene glycol, polytetramethylene glycol, and copolymer diols obtained by combining these. The number average molecular weight of the polymer diol is preferably 500 to 4000. By making the number average molecular weight 500 or more, more preferably 1500 or more, it is possible to prevent the texture from becoming hard. In addition, by making the number average molecular weight 4000 or less, more preferably 3000 or less, it is possible to maintain good strength of the PU resin. Examples of organic diisocyanates include aliphatic diisocyanates such as hexamethylene diisocyanate, dicyclohexylmethane diisocyanate, isophorone diisocyanate, and xylylene diisocyanate; aromatic diisocyanates such as diphenylmethane diisocyanate and tolylene diisocyanate; and these may be used in combination. Among these, from the viewpoint of light resistance, aliphatic diisocyanates such as hexamethylene diisocyanate, dicyclohexylmethane diisocyanate, and isophorone diisocyanate are preferably used. As the chain extender, an amine-based chain extender such as ethylenediamine and methylenebisaniline, or a diol-based chain extender such as ethylene glycol can be used. Also, a polyamine obtained by reacting a polyisocyanate with water can be used as the chain extender.

[0034] The PU resin can be used in the form of a solvent-based PU resin in which the PU resin is dissolved in an organic solvent such as N,N-dimethylformamide, or a water-dispersed PU resin in which the PU resin is emulsified with an emulsifier and dispersed in water. Among them, the water-dispersed PU resin is preferred because the PU resin can be easily filled in a fiber sheet in a fine form, the required performance of artificial leather such as texture and mechanical properties can be easily obtained even with a small amount of adhesion, and there is no need to use an organic solvent, thereby reducing the environmental load. That is, the water-dispersed PU resin can be impregnated into a fiber sheet in the form of a dispersion in which the PU resin is dispersed with a desired particle size (hereinafter also referred to as a PU resin dispersion), and the filling form of the PU resin in the fiber sheet can be well controlled by controlling the particle size. As the water-dispersible PU resin, a self-emulsifying PU resin containing a hydrophilic group in the PU molecule, a forced emulsifying PU resin in which the PU resin is emulsified with an external emulsifier, etc. can be used. A crosslinking agent can be used in combination with the water-dispersible PU resin to improve durability such as resistance to moist heat, abrasion, and hydrolysis. It is preferable to add a crosslinking agent to improve durability during flow dyeing, suppress fiber dropout, and obtain excellent surface quality. The crosslinking agent may be an external crosslinking agent added to the PU resin as an additive component, or an internal crosslinking agent that introduces a reactive group capable of forming a crosslinked structure into the PU resin structure in advance. Water-dispersible PU resins used in artificial leathers generally have a crosslinked structure to provide resistance to dyeing processes, and therefore tend to be difficult to dissolve in organic solvents such as N,N-dimethylformamide. Therefore, for example, when artificial leather is immersed in N,N-dimethylformamide at room temperature for 12 hours to dissolve the PU resin, and then the cross section is observed with an electron microscope or the like, if a resinous material not having a fibrous shape remains, the resinous material can be determined to be a water-dispersible PU resin.

[0035] In a preferred embodiment, from the viewpoint of easily controlling the cross-sectional PU resin area ratio and its standard deviation, the PU resin is filled using a PU resin dispersion, and the average primary particle diameter of the PU resin in the dispersion is preferably 0.1 μm or more and 0.8 μm or less, more preferably 0.1 μm or more and 0.6 μm or less, and even more preferably 0.2 μm or more and 0.5 μm or less. The average primary particle diameter is a value obtained by measuring the PU resin dispersion using a laser diffraction type particle size distribution measuring device ("LA-920" manufactured by Horiba, Ltd.). By making the average primary particle diameter of the PU resin 0.1 μm or more, the force of the PU resin holding the fibers in the fiber sheet together (i.e., the binder force) is improved, thereby obtaining an artificial leather having excellent mechanical strength. In addition, by making the average primary particle diameter of the PU resin 0.8 μm or less, the PU resin is prevented from agglomerating or becoming coarse, and the standard deviation of the cross-sectional PU resin area ratio can be easily controlled to 25% or less. By setting the average primary particle diameter of the PU resin in the PU resin dispersion to between 0.1 μm and 0.8 μm, the fibers that make up the artificial leather (especially its surface layer) are able to hold onto each other at more points, making it possible to achieve both a soft feel (bending resistance value) and excellent wrinkle resistance.

[0036] [Solid content concentration of PU resin dispersion] As described below, in a typical embodiment, the PU resin is impregnated in the form of an impregnation liquid such as a solution (for example, in the case of a solvent-dissolved type) or a dispersion (for example, in the case of a water-dispersed type). For example, the solid content concentration of the water-dispersed PU resin dispersion can be 10% by weight or more and 35% by weight or less, more preferably 15 to 30% by weight, and even more preferably 15 to 25% by weight. In one embodiment, the impregnation liquid is prepared and the fiber sheet is impregnated with the PU resin so that the ratio of the PU resin to 100% by weight of the fiber sheet is 15 to 50% by weight.

[0037] To the impregnation solution containing the PU resin (e.g., water-dispersed PU resin), additives such as stabilizers (UV absorbers, antioxidants, etc.), flame retardants, antistatic agents, pigments (carbon black, etc.) may be added as necessary. The total amount of these additives present in the artificial leather may be, for example, 0.1 to 10.0 parts by mass, or 0.2 to 8.0 parts by mass, or 0.3 to 6.0 parts by mass, relative to 100 parts by mass of the PU resin. Such additives will be distributed in the PU resin of the artificial leather. In the present disclosure, the values ​​referring to the size of the PU resin and the mass ratio to the fiber sheet are intended to include the additives (if used).

[0038] [Hot water soluble resin particles] In the case of impregnating a fiber sheet with an impregnation liquid containing a PU resin to fill the fiber sheet with the PU resin, a preferred embodiment involves impregnating the fiber sheet with an aqueous PU resin dispersion liquid containing hot water-soluble resin microparticles, and then heating to fix the PU resin, thereby obtaining a sheet-like product filled with the PU resin. In a post-process or dyeing process, the hot water-soluble resin microparticles are removed from the obtained fiber sheet with hot water, thereby partially dividing the continuous layer of the PU resin, making it porous, and achieving the effect of finely arranging the PU resin. Examples of hot water soluble resin microparticles include partially saponified PVA resin microparticles and fully saponified PVA resin microparticles. Since fully saponified PVA resin microparticles tend to be less soluble in water at room temperature (20°C) than partially saponified PVA resin microparticles, it is preferable to use fully saponified PVA resin microparticles as the hot water soluble resin microparticles. From the viewpoint of being less soluble in water at room temperature (20°C), the saponification degree of the fully saponified PVA resin microparticles is preferably 95 mol% or more, more preferably 98 mol% or more. In order to achieve both the force to bond and hold the fibers and the fine adhesion state of the PU resin, the average particle diameter (size) of the hot water soluble resin microparticles is preferably 1 μm or more and 8 μm or less, more preferably 2 μm or more and 6 μm or less, and even more preferably 2 μm or more and 4 μm or less. By setting the average particle size to 1 μm or more, the hot water soluble resin fine particles are less likely to aggregate, and by setting the average particle size to 8 μm or less, the hot water soluble resin fine particles are more likely to be impregnated into the fiber sheet. As the fine particles, "NL-05" manufactured by Mitsubishi Chemical Corporation can be used, and the fine particles can be made fine by the method described in JP-A-7-82384. The content of the hot water-soluble resin microparticles in the water-dispersed PU resin dispersion is preferably 1% by weight or more and 20% by weight or less, more preferably 2% by weight or more and 15% by weight or less, and even more preferably 3% by weight or more and 10% by weight or less. When the water-dispersed PU resin dispersion contains 1% by mass or more of hot water-soluble resin microparticles, the dispersion of the PU resin mass is easily promoted. On the other hand, when the water-dispersed PU resin dispersion contains 20% by mass or less of hot water-soluble resin microparticles, the microparticles do not aggregate, and the stability of the dispersion is easily maintained. In this specification, the term "hot water-soluble resin" refers to a resin that is poorly soluble in water at room temperature.

[0039] [Hot water soluble resin] When a sheet-like material filled with PU resin is obtained by impregnating a fiber sheet with a water-dispersed PU resin dispersion liquid containing hot water-soluble resin particles and then fixing the PU resin by heating, a step of adhering the hot water-soluble resin to the fiber sheet can be performed before impregnating the fiber sheet with the water-dispersed PU resin dispersion liquid containing hot water-soluble resin particles. The hot water-soluble resin (e.g., PVA resin) can be adhered by preparing an aqueous solution of the hot water-soluble resin, impregnating the fiber sheet with the aqueous solution, and then drying the fiber sheet. In a post-process or dyeing process, the hot water-soluble resin is removed from the obtained sheet-like material together with the hot water-soluble resin particles using hot water, which prevents the adhesion between the fiber and the PU resin, and breaks a part of the continuous layer of the PU resin, thereby making the adhesion state of the PU resin finer, and thus the texture of the artificial leather is easily improved. Examples of the hot water-soluble resin include partially saponified PVA resin and fully saponified PVA resin. Since the fully saponified PVA resin tends to be less likely to dissolve in water at room temperature (20°C) than the partially saponified PVA resin, it is preferable to use the fully saponified PVA resin as the hot water-soluble resin. From the viewpoint of being less likely to dissolve in water at room temperature (20°C), the saponification degree of the fully saponified PVA resin is preferably 95 mol% or more, more preferably 98 mol% or more. In order to increase the permeability of the hot water-soluble resin aqueous solution during impregnation, the polymerization degree is preferably 1000 or less, more preferably 700 or less.

[0040] [Fiber sheet] 1, the fiber sheet 1 includes at least a fiber layer (A) 12, and the scrim 11 and the fiber layer (B) 13 are optional and not essential elements. Therefore, the artificial leather of this embodiment may be a single layer of the fiber layer (A), a two-layered structure of the fiber layer (A) and a scrim or a fiber layer (B), or a three-layered structure of the fiber layer (A), a scrim, and a fiber layer (B). When the scrim 11 and / or the fiber layer (B) 13 are not included, the fiber layer (A) may be a single-layer fiber sheet filled with a PU resin, cut in half, as described below. In one embodiment, the fiber sheet has a single-layer structure that does not include a scrim. This is because cutting in half increases productivity. In another embodiment, the fiber sheet has a three-layer structure, and the scrim is the intermediate layer. For example, a three-layer structure in which a woven or knitted scrim 11 is sandwiched between a fiber layer (A) 12 constituting the first outer surface of the artificial leather and a fiber layer (B) 13 constituting the second outer surface of the artificial leather, and the fibers are intertwined between these layers, is preferable in terms of dimensional stability, tensile strength, tear strength, etc. In addition, according to the three-layer structure of the fiber layer (A), the fiber layer (B), and the scrim sandwiched therebetween, the fiber layer (A) and the fiber layer (B) can be individually designed, so that the diameter, type, etc. of the fibers constituting these layers can be freely customized according to the functions and uses required for the artificial leather. For example, by using ultrafine fibers for the fiber layer (A) and flame-retardant fibers for the fiber layer (B), it is possible to achieve both excellent surface quality and high flame retardancy.

[0041] When the fiber sheet includes a scrim, the scrim, which is a woven or knitted fabric, is preferably of the same polymer system as the fibers constituting the fiber layer (A) in terms of color uniformity by dyeing. For example, if the fibers constituting the fiber layer (A) are polyester-based, the fibers constituting the scrim are preferably polyester-based, and if the fibers constituting the fiber layer (A) are polyamide-based, the fibers constituting the scrim are preferably polyamide-based. In the case of knitted fabrics, the scrim is preferably a single knit knitted with a gauge of 22 or more and 28 or less. When the scrim is a woven fabric, it can achieve higher dimensional stability and strength than knitted fabrics. The weave of the fabric may be plain weave, twill weave, satin weave, etc., but plain weave is preferred in terms of cost and process aspects such as intertwining. The yarn constituting the woven fabric may be either monofilament or multifilament. The single fiber fineness of the yarn is preferably 5.5 dtex or less, since it is easy to obtain a soft artificial leather. The form of the yarn constituting the woven fabric is preferably a multifilament raw silk of polyester, polyamide, etc., or a textured yarn that has been subjected to a false twisting process and twisted with a twist number of 0 to 3000 T / m. The multifilament may be a normal one, and for example, 33 dtex / 6f, 55 dtex / 24f, 83 dtex / 36f, 83 dtex / 72f, 110 dtex / 36f, 110 dtex / 48f, 167 dtex / 36f, 166 dtex / 48f, etc. of polyester, polyamide, etc. are preferably used. The yarn constituting the woven fabric may be a multifilament long fiber. The weave density of the yarns in the woven fabric is preferably 30 to 150 threads / inch, more preferably 40 to 100 threads / inch, in order to obtain an artificial leather that is soft and has excellent mechanical strength. In order to provide good mechanical strength and a suitable feel, the weight of the woven fabric is 20 to 150 g / m 2 The presence or absence of false twist processing in the woven fabric, the number of twists, the single fiber fineness of the multifilament, the weaving density, and the like contribute to the entanglement of the fibers constituting the fiber layer (A) and the optional fiber layer (B) and the texture of the artificial leather as well as to mechanical properties such as seam strength, tear strength, tensile strength and elongation, and stretchability, and may be appropriately selected depending on the target physical properties and applications.

[0042] From the viewpoint of obtaining an artificial leather having a higher level of abrasion resistance, dyeability, and surface quality, in the artificial leather of this embodiment, the fiber layer (A) is preferably composed of fibers having an average diameter of 1 μm to 8 μm, more preferably 2 μm to 6 μm, and even more preferably 2 μm to 5 μm. If the average fiber diameter is 1 μm or more, the abrasion resistance, color development by dyeing, and light fastness are improved. On the other hand, if the average fiber diameter is 8 μm or less, the fiber number density is high, so that an artificial leather having a high density, a smooth surface feel, and better surface quality is easily obtained.

[0043] As fibers constituting the fiber layers constituting the artificial leather (fiber layer (A), and optional fiber layer (B) and additional layers), synthetic fibers such as polyester-based fibers such as polyethylene terephthalate, polybutylene terephthalate, polytrimethylene terephthalate, and polyamide-based fibers such as nylon 6, nylon 66, and nylon 12 are preferred. Among these, considering applications requiring durability such as the field of car seats, polyethylene terephthalate is preferred because the fiber itself does not yellow even when exposed to direct sunlight for a long period of time and has excellent color fastness. Furthermore, from the viewpoint of reducing the environmental load, as fibers constituting the fiber layers constituting the artificial leather, chemically recycled or material recycled polyethylene terephthalate, or polyethylene terephthalate using plant-derived raw materials, and the like, are more preferred.

[0044] In this specification, the term "single fiber dispersion" means that the fibers do not form fiber bundles, such as the island components in the islands-in-sea composite fiber described below. For example, fibers that can generate ultrafine fibers, such as islands-in-sea composite fibers (e.g., those using a copolymer polyester as the sea component and a regular polyester as the island component), are used to form a three-dimensional entanglement with a scrim, and then the fibers are subjected to a fiber-thinning treatment (removing the sea component of the islands-in-sea composite fiber by dissolving, decomposing, etc.), and the fibers obtained exist as fiber bundles in the fiber layer (A), and are not single fiber dispersion. As an example, islands-in-sea composite staple fibers having island components with a single fiber fineness of 0.2 dtex or equivalent and 24 islands / 1f are prepared, the fiber layer (A) is formed from the islands-in-sea composite staple fibers, and then a three-dimensional entanglement with the scrim is formed by needle punching or the like, and the three-dimensional entanglement is filled with a PU resin, and then the sea component is dissolved or decomposed, thereby obtaining ultrafine fibers with a single fiber fineness of 0.2 dtex or equivalent. In this case, the fibers are present in the fiber layer (A) in the form of a fiber bundle of 24 bundled fibers (corresponding to 4.8 dtex in the bundled state).

[0045] When the fiber layer (A) is composed of fibers dispersed as single fibers, the surface is excellent in smoothness, and when the outer surface of the fiber layer (A) is raised by buffing or the like, uniform nap is easily obtained. Furthermore, even if the adhesion rate of the PU resin is relatively low, a fuzz-like appearance called pilling is unlikely to occur due to friction, so that an artificial leather having better surface quality and abrasion resistance can be obtained. Furthermore, when the fibers are dispersed as single fibers, the fiber intervals tend to be narrow and uniform, so that good abrasion resistance can be obtained even if the PU resin is attached in a fine form. Examples of methods for dispersing the fibers as single fibers include a method in which fibers produced by a direct spinning method are made into a fiber sheet by a papermaking method, and a method in which the sea component of a fiber sheet produced from islands-in-the-sea type composite fibers is dissolved or decomposed to generate ultrafine fiber bundles, and then the surface of the ultrafine fiber bundles is subjected to the above-mentioned water flow dispersion treatment to promote the formation of single fibers from the ultrafine fiber bundles.

[0046] In the fiber layers constituting the artificial leather other than the fiber layer (A), the fibers may or may not be monofilament-dispersed, but in a preferred embodiment, the layers other than the fiber layer (A) are also composed of fibers in which monofilaments are dispersed. Since the fibers constituting the layers other than the fiber layer (A) are monofilament-dispersed, the thickness of the artificial leather becomes uniform, the processing precision is improved, and the quality is stabilized, which is preferable from the viewpoint of stabilizing the quality, and also from the viewpoint of homogenizing the appearance of the front and back of the artificial leather.

[0047] When the artificial leather is composed of only the fiber layer (A), the basis weight of the fiber constituting the fiber layer (A) is preferably 40 g / m from the viewpoint of mechanical strength such as abrasion resistance. 2 More than 500g / m 2 Less than 50 g / m 2 More than 370g / m 2 More preferably 60 g / m 2 More than 320g / m 2 The following is the result. When the artificial leather has a three-layer structure of a fiber layer (A), a scrim, and a fiber layer (B), the fiber layer (A) preferably has a basis weight of 10 g / m from the viewpoint of mechanical strength such as abrasion resistance. 2 More than 200g / m 2Less than 30 g / m 2 More than 170g / m 2 More preferably 60 g / m 2 More than 170g / m 2 The weight of the fibers constituting the fiber layer (B) is preferably 10 g / m2 or less from the viewpoints of cost and ease of production. 2 More than 200g / m 2 Less than 20 g / m, more preferably 20 g / m 2 More than 170g / m 2 The basis weight of the scrim is preferably 20 g / m2 or less from the viewpoints of mechanical strength and entanglement of the fiber layer with the scrim. 2 More than 150g / m 2 Less than 20 g / m, more preferably 20 g / m 2 More than 130g / m 2 More preferably, 30 g / m or less 2 More than 110g / m 2 The following is the result. The weight of the artificial leather filled with PU resin is preferably 50 g / m 2 More than 550g / m 2 Less than 60 g / m 2 More than 400g / m 2 More preferably, 70 g / m 2 More than 350g / m 2 The following is the result.

[0048] In one embodiment, the texture (bending softness value) of the artificial leather is preferably 28 cm or less, more preferably 6 cm or more and 26 cm or less, and even more preferably 8 cm or more and 22 cm or less. The bending softness value is an index showing the texture of the artificial leather. By setting the bending softness value to 28 cm or less, the moldability of the upholstery material or the interior material of the seat of the interior, automobile, aircraft, railway vehicle, etc. is improved, and the consumption performance is also improved, and it is easy to satisfy the needs of the market regarding the texture.

[0049] In one embodiment, the wrinkle resistance (wrinkle resistance rate) of the artificial leather according to JIS L 1059-1:2009 "Test method for wrinkle resistance of textile products-Part 1: Measurement of recovery of horizontal folding wrinkles (Monsanto method)" is preferably 60% or more, more preferably 70% or more, and even more preferably 80% or more. The wrinkle resistance (wrinkle resistance rate) is an index showing the recovery of creases of the artificial leather. For example, when the artificial leather is used as a skin material for the seats of automobiles, aircraft, railway vehicles, etc., fine creases are formed on the backrest by sitting in the seat for a long time, but by setting the wrinkle resistance (wrinkle resistance rate) to 60% or more, the creases are easily recovered and the surface quality is easily maintained even when the seat is used for a long time.

[0050] In one embodiment, the raised texture of the artificial leather, as evaluated by the method described below, is preferably at least grade 3. When the raised texture is at least grade 3, the surface quality of the artificial leather is satisfactory.

[0051] <Manufacturing method of artificial leather> An example of a method for producing the artificial leather of the present embodiment will be described below. An example of a method for producing an artificial leather according to the present embodiment includes the following steps: A step of forming a fiber web by mixing hot water soluble resin fibers with sea-island type short fibers as required, and then needle punching the resulting fiber sheet, and then removing the sea component to obtain a fiber sheet in which the island component single fibers are exposed; and a step of subjecting the obtained fiber sheet to a water jet dispersion treatment to obtain a fiber sheet in which single fibers are dispersed; The method may include the steps of: A step of impregnating the fiber sheet having the dispersed single fibers with a water-dispersed PU resin dispersion containing hot water-soluble resin particles, and then, if necessary, fixing the PU resin by using a combination of wet heat and microwaves to obtain a sheet-like material filled with the PU resin; and The method further includes a step of removing the hot-water-soluble resin fine particles and / or the hot-water-soluble resin fibers from the obtained sheet-like material using hot water. The fixing of the PU resin to the fibers using the combined use of moist heat and microwaves is preferably carried out under conditions of a steam temperature of 100° C. to 110° C., a microwave output of 10 kW, and a treatment time of 1 to 5 minutes.

[0052] Each step will be described in order below. [A step of forming a fiber web by optionally mixing hot water soluble resin fiber with sea-island staple fiber, and then needle punching the resulting fiber sheet, and then removing the sea component to obtain a fiber sheet in which island component single fibers are exposed] As a manufacturing method for each fiber layer (fiber layer (A), optional fiber layer (B), etc.) constituting the fiber sheet of the artificial leather, a direct spinning method (e.g., spunbond method and meltblown method) or a method of forming a fiber sheet using short fibers (e.g., dry method such as carding method and airlaid method, and wet method such as papermaking method) can be mentioned, and any of them can be suitably used. In the present embodiment, hot water soluble resin fibers and sea-island (SIF) short fibers are used as raw materials as necessary. After forming the fiber sheet, the fiber web is subjected to a water flow dispersion treatment described later, and the hot water soluble resin fibers of the sheet-like material obtained by filling the fiber sheet with PU resin are removed, so that the PU resin surrounding the hot water soluble resin fibers has a porous structure, and a flexible sheet-like material is obtained. When the artificial leather is composed of only the fiber layer (A), from the viewpoints of mechanical properties and texture (flexibility), the hot water soluble resin fibers are preferably 5 to 40 mass % of the total fiber mass, more preferably 5 to 30 mass %, and even more preferably 5 to 20 mass %. When the fiber layer has two or more layers, the mixing ratio may be the same as that of the fiber layer (A). When the fiber layer has two or more layers, it is preferable to mix hot water soluble resin fibers in the fiber layer (B) as in the fiber layer (A) in order to obtain a softer artificial leather. A fiber sheet produced using short fibers has small unevenness in basis weight and excellent uniformity, and is easy to obtain uniform nap, so it is suitable in terms of improving the surface quality of the artificial leather.

[0053] The means for forming the ultrafine fibers of the fiber sheet can be ultrafine fiber-developing fibers. By using ultrafine fiber-developing fibers, a stably entangled form of ultrafine fiber bundles can be obtained. Examples of ultrafine fiber-producing fibers that can be used include islands-in-sea fibers in which two thermoplastic resin components with different solvent solubility are used as a sea component and an island component, and the sea component is dissolved and removed using a solvent to convert the island components into ultrafine fibers, and peel-type composite fibers in which two thermoplastic resin components are alternately arranged radially or in multiple layers on the fiber cross section, and each component is peeled and divided to split into ultrafine fibers. Among these, islands-in-sea fibers are preferably used from the viewpoint of flexibility and texture of sheet-like products, since appropriate gaps can be provided between the island components, i.e., between the ultrafine fibers, by removing the sea component. Examples of islands-in-sea type fibers include islands-in-sea type composite fibers produced by using an islands-in-sea type composite spinneret to spin two components, a sea component and an island component, in mutual arrangement, and islands-in-sea type mixed fibers produced by mixing and spinning two components, a sea component and an island component. Island-in-sea type composite fibers are preferably used because they can produce ultrafine fibers with uniform fineness and ultrafine fibers of sufficient length that contribute to the strength of the sheet-like product. The sea component of the islands-in-sea fiber can be polyethylene, polypropylene, polystyrene, copolymerized polyesters copolymerized with sodium sulfoisophthalic acid, polyethylene glycol, etc., polylactic acid, etc. Among them, from the viewpoint of environmental consideration, copolymerized polyesters copolymerized with alkali-decomposable sodium sulfoisophthalic acid, polyethylene glycol, etc., which can be decomposed without using organic solvents, and polylactic acid are preferred. When using islands-in-sea fibers, it is preferable to perform the sea-removal treatment before adding PU resin to the fiber sheet. If the sea-removal treatment is performed before adding PU resin, the PU resin will adhere directly to the ultrafine fibers, and the ultrafine fibers will be strongly held, resulting in good abrasion resistance of the sheet-like material.

[0054] As a method for entangling the fibers or fiber bundles of the fiber web, a method can be adopted in which islands-in-the-sea fibers are cut to a predetermined fiber length to form staples, which are passed through a card and a cross-rapper to form a fiber web, and the fibers or fiber bundles are entangled by a hydroentanglement treatment called a needle punch or spunlace method. In the needle punch method, the number of barbs of the needle used is preferably 1 to 9. By using a barb number of 1 or more, an intertwining effect can be obtained and damage to the fibers can be suppressed. By using a barb number of 9 or less, damage to the fibers can be reduced and needle marks left on the artificial leather can be reduced, thereby improving the appearance of the product. Considering the effect on fiber entanglement and product appearance, the total depth of the barb (the length from the tip of the barb to the bottom of the barb) is preferably 0.05 mm or more and 0.10 mm or less. When the total depth of the barb is 0.05 mm or more, good hooking onto the fiber is obtained, enabling efficient fiber entanglement. Furthermore, when the total depth of the barb is 0.10 mm or less, needle marks left on the artificial leather are reduced, improving the quality. Considering the balance between the strength of the barb portion and fiber entanglement, the total depth of the barb is more preferably 0.06 mm or more and 0.08 mm or less. When entangling fibers using the needle punch method, the punch density should be within 300 threads / cm 2 More than 6000 pieces / cm 2 It is preferable to set the density to 1000 fibers / cm or less. 2 More than 6000 pieces / cm 2 It is more preferable to set it as follows: The fiber sheet obtained by the needle punching treatment can be dried, for example, using a hot air dryer at a temperature of 150° C. for 2 minutes to obtain a fiber sheet before sea-removal. The sea-removal treatment can be carried out by immersing the islands-in-sea fiber in a solvent and squeezing the solution. When the sea component is a copolymer polyester or polylactic acid, an aqueous alkali solution such as sodium hydroxide can be used as the solvent for dissolving the sea component. From the viewpoint of environmental consideration of the process, the sea-removal treatment using an aqueous alkali solution such as sodium hydroxide is preferred.

[0055] When a method using short fibers (staples) is selected, the short fiber length is preferably 13 mm to 102 mm, more preferably 25 mm to 76 mm, and even more preferably 38 mm to 76 mm in a dry method (carding method, airlaid method, etc.), and is preferably 1 mm to 30 mm, more preferably 2 mm to 25 mm, and even more preferably 3 mm to 20 mm in a wet method (papermaking method, etc.). For example, the aspect ratio (L / D), which is the ratio of length (L) to diameter (D) of short fibers used in a wet method (papermaking method, etc.), is preferably 500 to 2000, more preferably 700 to 1500. Such an aspect ratio is preferable because the short fibers have good dispersibility and openability in the slurry when the short fibers are dispersed in water to prepare a slurry, the fiber layer strength is good, and the fibers are shorter and easier to disperse as single fibers than in the dry method, so that the fibers are less likely to have a fluffy ball-like appearance called pilling due to friction. For example, the fiber length of a short fiber having a diameter of 4 μm is preferably 2 mm or more and 8 mm or less, more preferably 3 mm or more and 6 mm or less.

[0056] [A step of subjecting the obtained fiber sheet to a water flow dispersion treatment to obtain a fiber sheet in which single fibers are dispersed] The resulting fiber sheet is subjected to the above-mentioned water flow dispersion treatment to obtain a fiber sheet in which single fibers are dispersed. By carrying out the above-mentioned water flow dispersion treatment after the sea-removal step, it becomes possible to control the k-near distance ratio value (k=9, radius r=20 μm) between the cross sections of the single fibers constituting the fiber layer (A) in the cross section in the thickness direction of the artificial leather to 80% or less.

[0057] [A process of impregnating the fiber sheet having the dispersed single fibers with a water-dispersed PU resin dispersion containing hot water-soluble resin particles, and then, if necessary, fixing the PU resin by using a combination of wet heat and microwaves to obtain a sheet-like material filled with the PU resin] In this step, the fiber sheet is impregnated with an aqueous PU resin dispersion containing hot water-soluble resin particles, and then, if necessary, the PU resin is fixed using a combination of moist heat and microwaves to fill the fiber sheet with the PU resin. In a typical embodiment, the PU resin is impregnated in the form of an impregnation liquid such as a dispersion (for example, in the case of an aqueous dispersion). The concentration of the PU resin in the impregnation liquid can be, for example, 10 to 35% by mass. In one embodiment, the impregnation liquid is prepared and the fiber sheet is impregnated with the PU resin so that the ratio of the PU resin to 100% by mass of the fiber sheet is 15 to 50% by mass.

[0058] Water-dispersible PU resins are classified into forced emulsification type PU resins that are forcedly dispersed and stabilized using a surfactant, and self-emulsification type PU resins that have a hydrophilic structure in the PU molecular structure and are dispersed and stabilized in water even in the absence of a surfactant. Either type may be used in this embodiment, but it is preferable to use forced emulsification type PU resins from the viewpoint of imparting heat-sensitive coagulation properties described later. In this embodiment, the fiber sheet is impregnated with a water-dispersed PU resin dispersion containing hot water-soluble resin particles, but it is not preferable that the hot water-soluble resin particles are dissolved in the water-dispersed PU resin dispersion. On the other hand, since hot water-soluble resin particles are less likely to dissolve in an aqueous solution containing a surfactant than in water, a forced emulsification type PU resin dispersion containing a surfactant is more preferable than a self-emulsification type PU resin dispersion not containing a surfactant. The concentration of the water-dispersed PU resin (the content of the PU resin in the water-dispersed PU resin dispersion) is preferably 10 to 35% by mass, more preferably 15 to 30% by mass, and even more preferably 15 to 25% by mass, from the viewpoint of controlling the adhesion amount of the water-dispersed PU resin and the viewpoint that a high concentration promotes aggregation of the PU resin and reduces the stability of the impregnation liquid. Moreover, the water-dispersed PU resin dispersion is preferably one having a heat-sensitive coagulation property. By using a water-dispersed PU resin dispersion having a heat-sensitive coagulation property, the PU resin can be uniformly applied in the thickness direction of the fiber sheet. The heat-sensitive coagulation property refers to the property that the fluidity of the PU resin dispersion decreases and coagulates when a certain temperature (heat-sensitive coagulation temperature) is reached when the PU resin dispersion is heated. In the production of a sheet-like material filled with PU resin, the PU resin dispersion is impregnated into a fiber sheet, and then coagulated by dry heat coagulation, wet heat coagulation, hot water coagulation, or a combination of these, and then dried to impart the PU resin to the fiber sheet. As a method for coagulating a water-dispersed PU resin dispersion that does not exhibit heat-sensitive coagulation property, dry coagulation is a practical method for industrial production, but in that case, a migration phenomenon occurs in which the PU resin is concentrated on the surface layer of the sheet-like material, and the texture of the sheet-like material filled with the PU resin tends to harden. The heat-sensitive coagulation temperature of the water-dispersed PU resin dispersion is preferably 40 to 90° C. By setting the heat-sensitive coagulation temperature to 40° C. or higher, the stability of the PU resin dispersion during storage is improved, and adhesion of the PU resin to machines during operation can be suppressed. In addition, by setting the heat-sensitive coagulation temperature to 90° C. or lower, the migration phenomenon of the PU resin in the fiber sheet can be suppressed. In order to adjust the heat-sensitive coagulation temperature to the above range, a heat-sensitive coagulant may be added as appropriate. Examples of the heat-sensitive coagulant include inorganic salts such as sodium sulfate, magnesium sulfate, calcium sulfate, and calcium chloride, and radical reaction initiators such as sodium persulfate, potassium persulfate, ammonium persulfate, azobisisobutyronitrile, and benzoyl peroxide.

[0059] The aqueous PU resin dispersion can be impregnated or coated on a fiber sheet, and the PU resin can be coagulated by dry heat coagulation, wet heat coagulation, hot water coagulation, or a combination of these. The wet heat coagulation temperature is equal to or higher than the heat-sensitive coagulation temperature of the PU resin, and is preferably 40 to 200°C. By setting the wet heat coagulation temperature at 40°C or higher, more preferably at 80°C or higher, the time until the PU resin is coagulated can be shortened, and the migration phenomenon can be further suppressed. On the other hand, by setting the wet heat coagulation temperature at 200°C or lower, more preferably at 160°C or lower, thermal degradation of the PU resin and PVA resin can be prevented.

[0060] In addition, when using wet heat coagulation and microwaves in combination, the steam temperature during wet heat treatment is set to 100°C or higher and 110°C or lower, the treatment time is set to 1 minute to 5 minutes, and the microwave output during microwave treatment is set to 10 kW and the treatment time is set to 1 minute to 5 minutes, thereby promoting the porosity of the PU resin. The hot water coagulation temperature is set to the heat-sensitive coagulation temperature of the PU resin or higher, and is preferably set to 40 to 100°C. By setting the hot water coagulation temperature in hot water to 40°C or higher, more preferably 80°C or higher, the time until the PU resin is coagulated can be shortened and the migration phenomenon can be further suppressed. The dry coagulation temperature and the drying temperature are preferably set to 80 to 180°C. By setting the dry coagulation temperature and the drying temperature to 80°C or higher, more preferably 90°C or higher, excellent productivity can be achieved. On the other hand, by setting the dry coagulation temperature and the drying temperature to 180°C or lower, more preferably 160°C or lower, thermal deterioration of the PU resin and PVA resin can be prevented.

[0061] As described above, when the fiber sheet having the dispersed single fibers is impregnated with an aqueous PU resin dispersion containing hot water-soluble resin microparticles, the content of the hot water-soluble resin microparticles in the aqueous PU resin dispersion is preferably from 1 to 20% by weight, more preferably from 2 to 15% by weight, and even more preferably from 3 to 10% by weight. The inclusion of the hot water-soluble resin microparticles in the aqueous PU resin dispersion promotes further dispersion of the PU resin mass.

[0062] [Step of Removing the Hot Water-Soluble Resin Fine Particles and / or Hot Water-Soluble Resin Fibers from the Obtained Sheet-like Material Using Hot Water] The means for removing the hot water soluble resin from the sheet-like material includes, for example, a method of immersing the sheet in hot water at 60°C or higher, preferably 80°C or higher, and a method of removing the hot water soluble resin microparticles and / or hot water soluble resin fibers while circulating hot water at 80°C or higher before dyeing in a liquid jet dyeing machine. In particular, the method of removing the hot water soluble resin microparticles and / or hot water soluble resin fibers in a liquid jet dyeing machine is preferable in that the process of drying and winding the sheet-like material after removing the hot water soluble resin microparticles can be omitted, and production efficiency can be increased. In this embodiment, a soft sheet-like material is obtained by removing the hot water soluble resin microparticles from the sheet-like material after the PU resin is applied. The method for removing the hot water soluble resin microparticles and / or hot water soluble resin fibers is not particularly limited, but a preferred embodiment is, for example, to dissolve and remove the hot water soluble resin microparticles by immersing the sheet in hot water at 60 to 100°C and squeezing the liquid with a mangle or the like as necessary.

[0063] [Post-process] After filling the fiber sheet with PU resin and removing the hot water soluble resin particles and / or hot water soluble resin fibers, if the sheet does not contain a scrim, the sheet-like material filled with PU resin can be cut in half in the sheet thickness direction, thereby improving production efficiency. Furthermore, a lubricant such as a silicone dispersion may be applied to the sheet-like material filled with the PU resin before the nap raising process described below. Also, applying an antistatic agent before the nap raising process is a preferred embodiment in order to prevent grinding powder generated from the sheet-like material by grinding from accumulating on the sandpaper. In order to form naps on the surface of the sheet-like material, a nap raising treatment can be performed. The nap raising treatment can be performed by a method of grinding using sandpaper, a roll sander, or the like. In addition, by adding a lubricant such as silicone before the nap raising treatment, nap raising by surface grinding can be easily performed, and the surface quality can be very good. The artificial leather is preferably dyed to enhance the value of the sensory aspect (i.e., visual effect). The dye may be selected according to the type of fiber constituting the fiber sheet. For example, disperse dyes can be used for polyester fibers, and acid dyes or metal-containing dyes can be used for polyamide fibers, and further combinations thereof can be used. When dyeing with disperse dyes, reduction washing may be performed after dyeing. As the dyeing method, a normal method well known to dyeing and processing companies can be used. As the dyeing method, it is preferable to use a liquid flow dyeing machine, since the sheet-like material can be dyed and kneaded at the same time to soften the sheet-like material. The dyeing temperature is preferably 80 to 150°C, depending on the type of fiber. By setting the dyeing temperature to 80°C or higher, more preferably 110°C or higher, the dyeing into the fiber can be efficiently performed. On the other hand, by setting the dyeing temperature to 150°C or lower, more preferably 130°C or lower, the deterioration of the PU resin can be prevented. The artificial leather dyed in this manner is preferably subjected to soaping and, if necessary, reduction washing (i.e., washing in the presence of a chemical reducing agent) to remove excess dye. It is also a preferred embodiment to use a dyeing assistant during dyeing. The use of a dyeing assistant can improve the uniformity and reproducibility of the dyeing. In addition, a finishing agent treatment can be performed using a softener such as silicone, an antistatic agent, a water repellent, a flame retardant, a light fastener, an antibacterial agent, etc. in the same bath as dyeing or after dyeing.

[0064] The artificial leather of the present embodiment can be suitably used as an interior material having a very elegant appearance, such as a surface material for furniture, chairs, wall materials, seats, ceilings, and interiors in vehicle cabins such as automobiles, trains, and aircraft, uppers and trims of shoes such as shirts, jackets, casual shoes, sports shoes, men's shoes, and women's shoes, bags, belts, wallets, and the like, clothing materials used as parts of these materials, and industrial materials such as wiping cloths, polishing cloths, and CD curtains. EXAMPLES

[0065] The present invention will be described in detail below with reference to examples and comparative examples, but the scope of the present invention is not limited to these examples. The artificial leather samples according to the examples and comparative examples were evaluated for their physical properties, quality, etc., according to the following procedures and methods.

[0066] (1) Location of sample collection Figure 3 shows the locations where samples were collected. First, the fiber layer (A) or the artificial leather containing the fiber layer (A) is cut into 10 substantially uniform locations (sampling areas 1, 2, ...) in the machine direction (MD) in a strip shape (indicated by dotted lines). A thickness (t) cross section is prepared in each sampling area. The prepared thickness (t) cross section is subjected to a conductive treatment by coating with osmium atoms at 1 nm. In this cross section, in order to obtain the single fiber cross section k neighborhood distance ratio value (%) and the cross section PU resin area ratio (%), SEM images are taken at 10 substantially uniform locations in the CD direction perpendicular to the MD direction. In addition, in order to obtain the surface PU resin area ratio (%) in each sampling area, the first outer surface of the fiber layer (A) at 10 substantially uniform locations in the CD direction is subjected to a conductive treatment by coating with osmium atoms at 1 nm, and the SEM images of the first outer surface are taken. That is, 100 sheets of each image used to obtain the single fiber cross section k neighborhood distance ratio value (%) and the cross section PU resin area ratio (%) are prepared. In this case, the average value and standard deviation of each value are for 100 images. If the artificial leather is napped, the nap direction can be determined to be the MD direction. If the artificial leather is not napped and the MD direction is unknown, samples can be cut out in any one direction and in the direction perpendicular to it.

[0067] (2) Cross-sectional PU resin area ratio (%) and standard deviation Pretreatment The sample in the thickness direction cross section was cut to 1 cm x 0.5 cm (horizontal (x) x vertical (y)), and the internal space of the sample was embedded with epoxy resin (main agent: "Quetol 812" manufactured by Nissin EM Co., Ltd., fixing agent: "MNA" manufactured by Nissin EM Co., Ltd., accelerator: "DMP-30" manufactured by Nissin EM Co., Ltd.). The resin-embedded sample obtained was cut parallel to the thickness direction with a microtome to obtain a smooth cut surface. Next, the sample was left to stand in saturated vapor of ruthenium tetroxide for 4 hours, and the PU resin attached to the sample was electronically stained with ruthenium. Next, the sample was coated with 1 nm of osmium atoms to perform a conductive treatment. ·observation When the sample has a scrim, the deepest part (i.e., the part closest to the scrim) of the fiber layer (A) in the cut surface of the conductive sample is observed with a scanning electron microscope (SEM, Hitachi, Ltd.'s "SU8220"), with the fibers constituting the scrim excluded from the observation. When the sample does not have a scrim, the center of the artificial leather in the thickness direction in the cut surface of the conductive sample is observed with the SEM, with the observation conditions as follows: Acceleration voltage: 10 kV Detector: YAG-BSE (ring-shaped scintillator type backscattered electrons) Imaging magnification: 500x Observation field of view: approx. 230 μm x approx. 173 μm Image analysis The obtained SEM backscattered electron image is binarized using the image analysis software "ImageJ (version: 1.51j8) (National Institutes of Health, USA)" by the following method, and the average size of the PU resin is obtained. (i) Filter the SEM images. The processing conditions are as follows: Hand path filtering: Filter large structures down to 40 pixels, Filter small structures up to 3 pixels, Suppress stipes None, Tolerance of direction 5%, Autoscale after filtering on, Saturate image when autoscaling on, plus median filtering, radius: 4.0, one filter processing. (ii) Binarization is performed using the MaxEntropy method, and the black areas in the binarized SEM image are identified as PU resin. (iii) From the obtained binarized image, the area ratio of the PU resin for each section is determined. As shown in Figure 6, the obtained binarized image (1280 x 960 pixels, 1280 x 896 pixels excluding the band at the bottom of the image) is divided into 32 x 32 pixel sections (1120 sections in this case), and the sum of the areas of the PU resin distributed in each section is divided by the area of ​​each section using ImageJ's Analyze Particle function (conditions: Size = 0-infinity, Circularity = 0.00-1.00), and the cross-sectional PU resin area ratio (%) of each section is calculated. The number of pixels on the x and y axes of the target image is read, the section size is specified in pixel size, the number of divisions on the x and y axes is found, and the PU resin area % in each divided region is calculated. The area percentage of PU resin calculated from one SEM image is the average of the area percentages of PU resin for all sections of one SEM image, and the standard deviation is calculated using the formula shown in Figure 6. The cross-sectional PU resin area ratio (%) and standard deviation are the average values ​​of the PU resin area ratio and standard deviation calculated from one SEM image for 100 images. That is, as shown in Fig. 6, the standard deviation is first calculated for all sections divided into sections for one SEM image, and the average of the standard deviations calculated from each of the 100 SEM images is taken as the standard deviation.

[0068] (3) Percentage of the distance near the single fiber cross section k (%) As shown in Figure 5, the k-nearest neighbor method is a method in which k single fiber cross sections close to any one single fiber cross section are selected, and the k-th closest radius in Euclidean distance is used as the decision boundary. In this embodiment, in one SEM image, an area of ​​about 250 μm × about 186 μm is photographed with 640 × 480 pixels including the band at the bottom of the image (in this case, 1 pixel corresponds to about 0.40 μm × about 0.40 μm), and it is determined whether the k = 9th closest single fiber cross section is present within a distance of a radius of 20 μm from the approximate center of any single fiber cross section. The presence or absence of all single fiber cross sections in one SEM image is determined, and the single fiber cross section k = 9 neighborhood distance percentage value (%) is calculated using the following formula: Nearby distance percentage value (%) of single fiber cross section (k = 9) = {(number of single fiber cross sections in which the k = 9th closest single fiber cross section exists within a distance of a radius of 20 μm from approximately the center of the single fiber cross section) / (total number of single fiber cross sections in one SEM image)} × 100. The single fiber cross section k=9 neighborhood distance ratio value (%) is the average value of each value calculated from 100 SEM images. When the sample has a scrim, the deepest part (i.e., the part closest to the scrim) of the fiber layer (A) on the cut surface of the conductive sample is observed as the observation area, and the fibers constituting the scrim are not observed, and the sample is observed with a scanning electron microscope (SEM, "JSM-5610" manufactured by JEOL Ltd.). When the sample does not have a scrim, the center part of the artificial leather thickness direction on the cut surface of the conductive sample is observed with the SEM as the center point of the observation area. The presence of a single fiber cross-section in an SEM image can be identified by manual marking, as shown in Figure 4. The specific steps are as follows: [Step 1] In the SEM image (gray), a red (R) circle is marked on the fiber cross section, and then the coordinates of the fiber cross section are calculated. <Detailed Method> (i) Load the image using OpenCV (cv2 module for Python). (ii) Extract pixels whose RGB R is 220 or more and whose G and B are 100 or less. (iii) To remove noise, dilate (cv2.dilate with iteration=2) and erode (cv2.erode with iteration=2) the detected dots. (iv) Process the denoised image with cv2.connectedComponentsWithStats to get the centroid coordinates of the detected circles, which is the third of the four results. (v) The above center of gravity coordinates are set as the fiber cross section position. (vi) Furthermore, the distance between specific positions on the coordinate system is calculated. When the coordinates of fiber cross section A and fiber cross section B are (Ax, Ay) and (Bx, By), the Euclidean distance R between the two is R = √((Ax-Bx) 2 +(Ay-By) 2 ) is calculated. [Step 2] For all fiber cross sections, the Euclidean distance (k-nearest neighbor distance: matrix distance) to the k-th nearest fiber cross section is calculated. <Detailed Method> (i) Calculate the distance between the coordinates of fiber cross section A and other cross sections. (ii) The calculated distances are sorted in ascending order. (iii) The kth distance in the list is defined as the kth nearest neighbor distance. [Step 3] The number of cross sections with a k-nearest neighbor distance of R or less is divided by the total number of fiber cross sections to obtain the k-nearest neighbor distance ratio value in the SEM image. When there are a large number of SEM images, the positions of the fiber cross sections can be identified in place of manual marking by machine learning (deep learning) that uses images containing teacher data (correct labels) in which red (R) dots are marked on fiber cross sections as training data and performs class classification at the pixel level using semantic segmentation using a fully convolutional network (FCN) method (Jonathan Long, Evan Shelhamer, and Trevor Darrel (2015): Fully Convolutional Networks for Semantic Segmentation. In The IEEE Conference on Computer Vision and Pattern Recognition (CVPR)).

[0069] (4) Average diameter (μm) of the single fibers constituting the fiber layer (A) The average diameter of the fibers constituting the fiber layer (A) is determined as the arithmetic mean value of the measurements of 100 fibers, which are randomly selected from the cross section of the thickness direction of the fiber layer (A) constituting the artificial leather, by taking 10 SEM images at a magnification of 1500 times using a scanning electron microscope (SEM, "JSM-5610" manufactured by JEOL Ltd.), measuring the cross-sectional diameter of each single fiber, and then measuring the average diameter of the 100 fibers. When the observed shape of the cross section of a single fiber is not circular, the fiber diameter is the distance between the outer circumferences of a straight line perpendicular to the midpoint of the longest diameter of the cross section of the single fiber. Fig. 2 is a conceptual diagram for explaining how to determine the fiber diameter. For example, when the cross section A of the fiber is elliptical as shown in Fig. 2, the fiber diameter is the outer periphery distance c on a straight line b perpendicular to the midpoint p of the longest diameter a of the cross section A in the observed image.

[0070] (5) Calculation of texture (flexibility) The sample was cut into a square of 20 cm x 20 cm to be used as a measurement sample. The measurement sample was placed on a horizontal plane, and the vertices of the square were designated as A, B, C, and D, and the vertices A and C, which faced each other on a diagonal line, were overlapped. The vertex A was placed on a horizontal plane, and the vertex C was overlapped with the vertex A. Next, the vertex C was gradually moved away from the vertex A along the diagonal line AC while in contact with the measurement sample, and the point where the vertex C left the measurement sample surface was designated as point E, and the distance between point E and vertex C was designated as the bending softness value 1. The vertex A was replaced with the vertex B, and the vertex C was replaced with the vertex D, respectively, and the bending softness value 2 was measured in the same manner as above. The arithmetic average value of the bending softness value 1 and the bending softness value 2 was designated as the texture (bending softness value) of the sample. In addition, when the artificial leather is a single layer, the average value for 10 samples was designated as the texture (bending softness value). When the artificial leather has a two-layer structure or a three-layer structure, the texture (stiffness / softness value) is the average value of five samples measured with the fibrous layer (A) constituting the artificial leather facing up and five samples measured with the fibrous layer (A) facing down.

[0071] (6) Wrinkle resistance (wrinkle resistance rate) Based on the description of JIS L 1059-1:2009 "Testing method for wrinkle resistance of textile products - Part 1: Measurement of recovery from horizontal folding wrinkles (Monsanto method)", a 10N load device is used to measure the wrinkle recovery angle of 10 pieces of single-layer artificial leather, and the average value of the 10 pieces is calculated using the formula described in 10 "Calculation of wrinkle recovery angle and wrinkle resistance rate". If the artificial leather has a two-layer or three-layer structure, the wrinkle resistance (wrinkle resistance rate) is the average value of five samples measured with the fiber layer (A) constituting the artificial leather on the upper surface and five samples measured with the fiber layer (A) on the lower surface. A wrinkle resistance rate of 60% or more is considered good.

[0072] (7) Brushed feel A total of 20 healthy adult evaluators, 10 males and 10 females, visually and sensorily evaluated the samples on a 7-point scale according to the following criteria, with the most common evaluation being the brushed feel. A grade of 3.0 to 7.0 for the brushed feel is considered good (passed). Grade 7: Very strong brushed feel and very good appearance. Level 6: A rating between levels 7 and 5. Grade 5: Strong brushed feel and good appearance. Level 4: A rating between Level 5 and Level 3. Grade 3: Brushed feel and satisfactory appearance. Level 2: A rating between Level 3 and Level 1. Grade 1: No brushed feel and poor appearance. The average value of the 10 samples is taken as the grade of the raised texture.

[0073] (8) Ratio of PU resin to fiber sheet The ratio of the PU resin to the fiber sheet was measured by the following method. The mass of the fiber sheet before impregnation with PU resin is A (g). The fiber sheet is impregnated with PU resin dispersion, then heated and dried at 130°C using a pin tenter dryer, then softened while immersed in hot water heated to 90°C, and then dried to obtain a fiber sheet filled with PU resin (hereinafter also referred to as "resin-filled fiber sheet"). The mass of the resin-filled fiber sheet is B1 (g). The ratio of PU resin (C1) is calculated using the following formula. C1 = (B1 - A) / A x 100 (wt%)

[0074] (9) Average primary particle size of PU resin in PU resin dispersion Measurements were made using a laser diffraction particle size distribution analyzer (LA-920, manufactured by Horiba, Ltd.) in accordance with the measurement manual for the device, and the median diameter was taken as the average primary particle diameter.

[0075] (10) Degree of saponification of hot water soluble resin particles contained in PU resin dispersion Measurement was performed in accordance with JIS K 6726 (1994) 3.5.

[0076] (11) Degree of polymerization of hot water soluble resin particles contained in PU resin dispersion Measurement was performed in accordance with JIS K 6726 (1994) 3.7.

[0077] (12) Average particle size (μm) of hot water soluble resin particles contained in PU resin dispersion As the fine particles, "NL-05" manufactured by Mitsubishi Chemical Corporation can be used, and the fine particles of hot water soluble resin were refined according to the method described in JP-A-7-82384.

[0078] (13) Disturbance of the water flow discharged from the nozzle in the water flow dispersion process The disturbance of the water flow discharged from the nozzle in the water flow dispersion treatment was measured by the following method. The water flow discharged from the nozzle is photographed with a single-lens camera (Nikon Corporation's "D600") equipped with a telecentric lens (Sill Optics GmbH & Co. KG's "S5LPJ007 / 212") to obtain image data. The image data is imported into a PC, and the water flow is cut out in a range of 25 mm to 35 mm from the nozzle outlet, and the water flow diameter is measured for each pixel row (approximately 6 μm) in the width direction of the water flow. From all the measured data, the average water flow diameter W and standard deviation σ in the range of 25 mm to 35 mm from the nozzle outlet are calculated, and the disturbance is calculated using the following formula. Disturbance(%)=σ(mm) / W(mm)×100 The disturbance is the average value obtained from five pieces of image data.

[0079] [Example 1] A sea component was made of polyethylene terephthalate copolymerized with 8 mol% sodium 5-sulfoisophthalate, and an island component was made of polyethylene terephthalate. The sea component was 20 mass% and the island component was 80 mass%, and an islands-in-sea type composite fiber was obtained with an island number of 16 islands / 1f and an average fiber diameter of 18 μm. The obtained islands-in-sea type composite fiber was cut into a fiber length of 51 mm to form staples, which were passed through a card and a cross wrapper to form a fiber web, and a fiber sheet was obtained by needle punching. The obtained fiber sheet was hot-air dried at 150°C for 2 minutes using a hot air dryer to obtain a basis weight of 600 g / m. 2 A single layer fiber sheet of 1000 μm was obtained. The obtained fiber sheet was immersed in a 50 g / L aqueous sodium hydroxide solution heated to 50° C. for 60 minutes to remove the sea component from the islands-in-sea composite fiber. The average diameter of the single fibers constituting the fiber sheet after the sea component removal was 4 μm. Next, a high-velocity water stream was sprayed from the upper layer and from the lower layer at a pressure of 4 MPa using a straight-flow nozzle with a nozzle hole spacing of 0.25 mm, a disturbance of 7%, a hole diameter of 0.10 mm, and three rows of nozzle holes, promoting the breakdown of the fibers that make up the fiber bundle into single fibers at a pressure of 4 MPa from the upper layer and 3 MPa from the lower layer. Next, the fiber sheet was impregnated with an impregnation liquid containing 9.0% of a polyether-based water-dispersed PU dispersion "AE-12" (manufactured by NICCA Chemical Co., Ltd.) (solid concentration: 35 mass%) having an average primary particle size of 0.3 μm, 3.0% by weight of anhydrous Glauber's salt as an impregnation aid (mass % of solid content), and PVA resin fine particles "NL-05" (manufactured by Mitsubishi Chemical Corporation) having an average particle size of 3 μm, and then coagulated with wet heat at 100° C. for 5 minutes and dried with hot air at 130° C. for 5 minutes using a hot air dryer. The sheet was then immersed in hot water heated to 95°C to extract and remove the impregnated anhydrous sodium sulfate and PVA resin particles, yielding a sheet filled with water-dispersible PU resin, the ratio of which to the total fiber mass of the sheet was 30% by mass. The sheet-like material was then cut in half perpendicular to the thickness direction using a half-cutting machine with an endless band knife, and the surface that was not cut in half was raised using #400 emery paper, and then dyed with a blue disperse dye ("BlueFBL" manufactured by Sumitomo Chemical Co., Ltd.) with a dye concentration of 5.0% owf using a liquid jet dyeing machine at 130°C for 15 minutes, and reduction washed. Then, it was dried at 100°C for 5 minutes using a hot air dryer to obtain a single-layer artificial leather.

[0080] [Example 2] An artificial leather was obtained in the same manner as in Example 1, except that the water pressure from the upper layer side in the water flow dispersion treatment was changed to 4.0 MPa.

[0081] [Example 3] An artificial leather was obtained in the same manner as in Example 2, except that the ratio of the PU resin to the fiber sheet was 44% by mass.

[0082] [Example 4] An artificial leather was obtained in the same manner as in Example 2, except that the ratio of the PU resin to the fiber sheet was 47% by mass.

[0083] [Example 5] An artificial leather was obtained in the same manner as in Example 2, except that the ratio of the PU resin to the fiber sheet was 17% by mass.

[0084] [Example 6] An artificial leather was obtained in the same manner as in Example 2, except that after the PU resin impregnation, wet heat treatment was performed under conditions of a steam temperature of 110°C for a treatment time of 3 minutes, and microwave treatment was performed under conditions of a microwave output of 10 kW for a treatment time of 3 minutes.

[0085] [Example 7] An artificial leather was obtained in the same manner as in Example 2, except that the islands-in-the-sea type composite fiber was mixed with PVA fiber and the ratio of the PVA fiber to the total fiber amount was 10 mass %.

[0086] [Example 8] An artificial leather was obtained in the same manner as in Example 2, except that the islands-in-the-sea type composite fiber was mixed with PVA fiber and the ratio of the PVA fiber to the total fiber amount was 18 mass %.

[0087] [Example 9] An artificial leather was obtained in the same manner as in Example 2, except that the islands-in-the-sea type composite fiber was mixed with PVA fiber and the ratio of the PVA fiber to the total fiber amount was 25 mass %.

[0088] [Example 10] An artificial leather was obtained in the same manner as in Example 2, except that the islands-in-the-sea type composite fiber was mixed with PVA fiber and the ratio of the PVA fiber to the total fiber amount was 35 mass %.

[0089] [Example 11] An artificial leather was obtained in the same manner as in Example 2, except that the nozzle hole interval in the water jet dispersion treatment was changed to 0.50 mm and the number of rows of the nozzle holes was changed to two.

[0090] [Example 12] An artificial leather was obtained in the same manner as in Example 2, except that the nozzle hole interval in the water jet dispersion treatment was changed to 0.50 mm and the number of rows of nozzle holes was changed to 1.

[0091] [Example 13] An artificial leather was obtained in the same manner as in Example 2, except that the nozzle hole interval in the water jet dispersion treatment was changed to 0.90 mm and the number of rows of nozzle holes was changed to one.

[0092] [Example 14] An artificial leather was obtained in the same manner as in Example 1, except that in the water jet dispersion treatment, the nozzle hole interval was changed to 0.50 mm, the nozzle hole diameter was changed to 0.15 mm, and the number of rows of the nozzle holes was changed to two.

[0093] [Example 15] An artificial leather was obtained in the same manner as in Example 1, except that in the water jet dispersion treatment, the nozzle hole interval was changed to 0.50 mm, the nozzle hole diameter was changed to 0.22 mm, and the number of rows of the nozzle holes was changed to two.

[0094] [Example 16] After the PU resin impregnation, a wet heat treatment was performed under conditions of a steam temperature of 110°C for a treatment time of 3 minutes, and a microwave treatment was performed under conditions of a microwave output of 10 kW for a treatment time of 3 minutes. An artificial leather was obtained in the same manner as in Example 2, except that PVA fiber was mixed with the islands-in-sea type composite fiber and the ratio of PVA fiber to the total fiber amount was 10 mass%.

[0095] [Example 17] After the PU resin impregnation, a wet heat treatment was performed under conditions of a steam temperature of 110°C for a treatment time of 3 minutes, and a microwave treatment was performed under conditions of a microwave output of 10 kW for a treatment time of 3 minutes, and an artificial leather was obtained in the same manner as in Example 2, except that PVA fiber was mixed with the islands-in-sea type composite fiber, the ratio of PVA fiber to the total fiber amount was 10 mass%, and the disturbance of the water flow dispersion treatment was 13%.

[0096] [Example 18] An artificial leather was obtained in the same manner as in Example 2, except that the disturbance in the water jet dispersion treatment was set to 13%.

[0097] [Example 19] An artificial leather was obtained in the same manner as in Example 2, except that the disturbance in the water jet dispersion treatment was set to 11%.

[0098] [Example 20] An artificial leather was obtained in the same manner as in Example 2, except that the disturbance in the water jet dispersion treatment was set to 16%.

[0099] [Example 21] An artificial leather was obtained in the same manner as in Example 2, except that the average particle size of the PVA particles in the PU resin impregnation was set to 5 μm and the disturbance in the water flow dispersion treatment was set to 13%.

[0100] [Example 22] An artificial leather was obtained in the same manner as in Example 2, except that the average particle size of the PVA particles in the PU resin impregnation was set to 7 μm and the disturbance in the water flow dispersion treatment was set to 13%.

[0101] [Example 23] An artificial leather was obtained in the same manner as in Example 2, except that the islands-in-the-sea type composite fiber was mixed with PVA fiber and the ratio of the PVA fiber to the total fiber amount was 45 mass %.

[0102] [Example 24] An artificial leather was obtained in the same manner as in Example 1 or 2, except that the water pressure from the upper layer side in the water flow dispersion treatment was changed to 12.0 MPa.

[0103] [Comparative Example 1] An artificial leather was obtained in the same manner as in Example 2, except that the PVA resin fine particles were not added to the PU resin impregnation liquid.

[0104] [Comparative Example 2] An artificial leather was obtained in the same manner as in Example 2, except that no PVA resin fine particles were added to the PU resin impregnation solution and the disturbance in the water flow dispersion treatment was set to 13%.

[0105] [Comparative Example 3] An artificial leather was obtained in the same manner as in Example 2, except that the water flow dispersion treatment was not performed, no PVA resin fine particles were added to the PU resin impregnation solution, and after the PU resin impregnation, the wet heat treatment was performed under conditions of a water vapor temperature of 110°C for a treatment time of 3 minutes, and the microwave treatment was performed under conditions of a microwave output of 10 kW for a treatment time of 3 minutes.

[0106] [Comparative Example 4] An artificial leather was obtained in the same manner as in Example 2, except that the water jet dispersion treatment was not carried out.

[0107] [Comparative Example 5] An artificial leather was obtained in the same manner as in Example 2, except that no PVA resin microparticles were added to the PU resin impregnation solution, PVA fibers were mixed with the islands-in-the-sea type composite fibers, and the ratio of PVA fibers to the total fiber amount was 10 mass%.

[0108] [Comparative Example 6] An artificial leather was obtained in the same manner as in Example 2, except that the water pressure from the upper layer side in the water flow dispersion treatment was changed to 0.7 MPa.

[0109] [Comparative Example 7] An artificial leather was obtained in the same manner as in Example 2, except that the ratio of the PU resin to the fiber sheet was 58% by mass.

[0110] [Comparative Example 8] An artificial leather was obtained in the same manner as in Example 2, except that the ratio of the PU resin to the fiber sheet was 13 mass %.

[0111] [Comparative Example 9] An artificial leather was obtained in the same manner as in Example 2, except that the average particle size of the PVA particles in the PU resin impregnation was 10 μm, the disturbance of the water flow dispersion treatment was 13%, and the ratio of PU resin to the fiber sheet was 13 mass%.

[0112] The results of Examples 1 to 24 and Comparative Examples 1 to 9 are shown in Table 1 below.

[0113] [Table 1]

[0114] These results show that in each Example, the polyurethane area ratio (cross-sectional PU resin area ratio) in the thickness direction cross section was 15% or more and 30% or less, and the standard deviation of the cross-sectional PU resin area ratio was 25% or less, and the PU resin and single fibers were distributed in a specific structure, resulting in an artificial leather that combines texture (stiffness / softness value) and wrinkle resistance (wrinkle resistance rate). [Industrial Applicability]

[0115] The artificial leather according to the present invention is excellent in texture (bending resistance value) and wrinkle resistance (wrinkle resistance rate), and therefore can be suitably used for the upholstery or interior materials of seats for interiors, automobiles, aircraft, railway cars, etc., clothing products, etc. Specifically, the artificial leather according to the present invention can be suitably used as an interior material having a very elegant appearance as a upholstery material for furniture, chairs, wall materials, seats, ceilings, interiors, etc. in vehicle compartments of automobiles, trains, aircraft, etc., uppers and trims of shoes such as shirts, jackets, casual shoes, sports shoes, men's shoes, women's shoes, etc., clothing materials used in parts of bags, belts, wallets, etc., and industrial materials such as wiping cloths, polishing cloths, CD curtains, etc. [Explanation of symbols]

[0116] 1. Fiber sheet 11 Scrims (Optional) 12 Fiber layer (A) 13 Fiber layer (B) A Cross section of a fiber when the cross section is elliptical a Longest diameter of cross section A b A straight line that passes through the midpoint p of the longest diameter a and is perpendicular to the longest diameter a c Distance between the outer circumferences on line b p Midpoint of the longest diameter a MD machine direction CD width (horizontal) direction t Thickness of artificial leather

Claims

1. An artificial leather comprising a fiber sheet and a polyurethane resin, the fiber sheet comprising at least a fiber layer (A) constituting a first outer surface of the artificial leather, the fiber layer (A) having a cross-sectional polyurethane resin area ratio of 15% or more and 30% or less in a thickness direction cross section, and the cross-sectional polyurethane resin area ratio having a standard deviation of 25% or less.

2. 2. The artificial leather according to claim 1, wherein the k-neighborhood distance ratio (k=9, radius r=20 μm) between the cross sections of the single fibers constituting the fiber layer (A) in the thickness direction cross section of the artificial leather is 10% or more and 80% or less.

3. 3. The artificial leather according to claim 1 or 2, wherein the fiber sheet has a two or more layer structure composed of a fiber layer (A) constituting the first outer surface and a scrim and / or a fiber layer (B) in contact with the fiber layer (A).

4. The artificial leather according to any one of claims 1 to 3, wherein the average diameter of the single fibers constituting the fiber layer (A) is 1.0 µm or more and 8.0 µm or less.

5. The artificial leather according to any one of claims 1 to 4, wherein the polyurethane resin is a water-dispersible polyurethane resin.

6. The artificial leather according to any one of claims 1 to 5, wherein the adhesion rate of the polyurethane resin to the fiber sheet is 15% by mass or more and 50% by mass or less.

7. The artificial leather according to any one of claims 1 to 6, which has a bending resistance of 28 cm or less.

8. The artificial leather according to any one of claims 1 to 7, having a wrinkle resistance rate of 60% or more according to JIS L 1059-1:2009 "Test method for wrinkle resistance of textile products - Part 1: Measurement of recovery from horizontal folding wrinkles (Monsanto method)".

9. The artificial leather according to any one of claims 1 to 8, wherein the fiber sheet is made of polyester fiber.

10. The following steps: a step of forming a fiber web from the islands-in-sea type staple fibers, and then needle-punching the resulting fiber sheet to obtain a sea-removal treatment to obtain a fiber sheet in which island component single fibers are exposed; a step of subjecting the obtained fiber sheet to a water jet dispersion treatment in which water is sprayed at a water pressure of 1.0 to 10.0 MPa to obtain a fiber sheet in which single fibers are dispersed; a step of impregnating the fiber sheet having the dispersed single fibers with a water-dispersed polyurethane resin dispersion containing hot water-soluble resin particles having an average particle size of 1 μm to 8 μm, and then fixing the polyurethane resin by heating to obtain a sheet-like material filled with the polyurethane resin; and a step of removing the hot-water-soluble resin fine particles from the obtained sheet-like material using hot water; The method for producing the artificial leather according to any one of claims 1 to 9, comprising:

11. The manufacturing method described in claim 10, in the process of obtaining a sheet-like material filled with the polyurethane resin, the polyurethane resin is fixed to the fibers by drying in combination with microwaves after moist heat treatment.

12. The method according to claim 10 or 11, wherein the fiber web contains hot-water soluble resin fibers.

13. The method according to claim 12, wherein the hot-water-soluble resin particles are polyvinyl alcohol resin.

14. The manufacturing method according to any one of claims 10 to 13, wherein the water jet dispersion treatment is carried out using a plurality of nozzles having a nozzle hole interval of 1.0 mm or less and a nozzle hole diameter of 0.05 mm or more and 0.30 mm or less.

15. The method according to any one of claims 10 to 14, wherein the water jet dispersion treatment is carried out using a plurality of nozzles that eject water jets with a disturbance of 10% or more.

16. The method according to any one of claims 11 to 15, wherein the solid content concentration in the aqueous polyurethane resin dispersion is 10% by weight or more and 35% by weight or less.

17. The method according to any one of claims 11 to 16, wherein the content of the hot water-soluble resin fine particles in the water-dispersed polyurethane resin dispersion is 1% by weight or more and 20% by weight or less.

Citation Information

Patent Citations

  • JP1973005889B

  • Production of suede like artificial leather

    JP1987062991A

  • Leather-like sheet-shaped product and method for producing the same

    JP2010248683A

  • Method for producing sheet-shaped material

    JP2014025165A

  • Artificial leather and method for producing the same

    JP2016069790A